Evaluating the potential of thermal evaporation for onsite retention of per- and polyfluoroalkyl substances (PFAS) in landfill leachate - Alina S. Timshina; Allison R. Cerlanek; Ashley M. Lin; Timothy G. Townsend; John A. Bowden (Waste Management, 2026)

Synergistic Effects of Biochar and Biofertilizers on Sustainable Crop Production: A Systematic Review - S. M. Shamiul Alam; Lin Wei; Tochukwu Ozor; Saurav Marahatta (International Journal of Plant Production, 2026)
The growing demand for food and the environmental concerns raised by excessive chemical fertilizer use have increased interest in sustainable soil fertility management practices. Biofertilizers (BFs) contain beneficial microorganisms that improve nutrient cycling and support plant growth. Biochar (BC), a carbon (C) rich material produced from biomass pyrolysis, improves soil structure, nutrient retention, and soil health. Although both BF and BC have been extensively studied individually, few studies have examined their combined effects. This systematic review summarizes the results from 66 peer-reviewed studies published between 2015 and 2025. The studies were identified through the Web of Science Core Collection and screened following Preferred Reporting Items for Systematic Reviews and MetaAnalyses (PRISMA) guidelines. The review evaluates the combined effects of BC and BF application on soil quality, nutrient availability, crop growth, stress tolerance, and environmental emissions. It was found that the combined application of BC and BFs improved microbial activity, soil enzyme activity, nutrient uptake, crop biomass, and yield more effectively than single applications. The reported reductions in global warming potential (GWP) and greenhouse gas intensity (GHGI) also indicated their environmental benefits. However, the effectiveness of BC+BF co-application varied, depending on biochar feedstock, pyrolysis conditions, microbial strains, application methods, and soil properties. Current challenges for co-application of BC and BFs include determining optimal application rates, selecting suitable biochar materials, and the limited availability of long-term and large-scale field studies. Overall, BC and BFs co-application shows strong potential for improving agricultural sustainability and resilience. Future studies should focus on long-term field experiments across different agroecological conditions.

Preliminary Investigation of Phosphorus-Use Efficiency in Mungbean (Vigna radiata): A Comparative RNA-Seq Study - Deepali Kothari; Muraleedhar S. Aski; S. Premakumar; Bidwan Rath; Nirmala Pargaien; Lalit Mohan Tewari; Shouvik Das; Gyan Prakash Mishra; Gyanendra Singh; Prachi Shripatrao Yadav; Ya-Ping Lin; Roland Schafleitner; et al. (Indian Journal of Genetics and Plant Breeding, 2026)

Storage timescales and the crystal growth history recorded in the layered reservoir of the Unit 3 Kulanaokuaiki Tephra Member of the Uēkahuna Ash from Kīlauea volcano - Abigail R. Nalesnik; Kendra J. Lynn; Timothy R. Rose; Jessica M. Warren; Dawn C. S. Ruth; Kuan-Yu Lin; Donald A. Swanson (Contributions to Mineralogy and Petrology, 2026)
The Kulanaokuaiki Tephra Unit 3 (900 C.E.) was a subplinian basaltic scoria eruption, the largest known to have occurred at Kīlauea’s summit. The initiation mechanism and cause(s) of this highly hazardous eruption remain poorly understood, particularly as this style of activity has not been observed in the modern period. We use olivine diffusion timescales from Fe-Mg and lithium zoning to assess magma storage timescales and evaluate evidence for mixing prior to eruption. Of the 200 crystals assessed, 55% are normally zoned for forsterite and 45% are non-zoned. Zoned crystals (> 1 mm) ( n = 96) have average compositions of Fo 89 cores and Fo 81 rims, while small crystals 0.5–1 mm ( n = 14) have Fo 85 cores and Fo 82 rims. Modeled Fo diffusion timescales range from n = 17), reflecting growth processes and precluding their use for diffusion studies. Overall, our Unit 3 olivine dataset displays no evidence of magmatic priming shortly prior to eruption, unlike prior observations for the basaltic subplinian eruption of the Keanakāko‘i Tephra Unit E (1650 C.E.). Thus, explosive eruption magmas may be stored for considerably longer than previously thought, and magmatic priming is not a necessary precursor for Kīlauea’s explosive eruptions. We hypothesize that gas-driven filter pressing from crystallization of microlites and macrocrysts in the reservoir slurry contributed to the explosivity of the Unit 3 eruption.

Dietary Patterns Associated With Weight Loss Among Patients With Colorectal Cancer During the First 6 Months After Diagnosis: A Cross-Sectional Analysis From the ColoCare Study - Rachel Hoobler; Fred K. Tabung; Tengda Lin; Biljana Gigic; Kristen S. Smith; Kary Woodruff; Sylvia L. Crowder; Sheetal Hardikar; Doratha A. Byrd; Adriana M. Coletta; Alejandro Sanchez; Amandine Chaix; et al. (Journal of the Academy of Nutrition and Dietetics, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Solvent effects on quercetin incorporation, release behavior, and antibacterial efficacy in gelatin/dialdehyde cellulose composite films: A comparative study - Myat Noe Khin; Shabbir Ahammed; Chong Yuen Yuen; Tariq Aziz; Maryam M. Alomran; Ashwag Shami; Fahad Al-Asmari; Maher S. Alwethaynani; Lin Lin (Food Hydrocolloids, 2026)

Assessing Potential Data Sources for Landscape-scale Terrestrial Biodiversity Indicators - Tom Bradfer-Lawrence; Meriel Harrison; Adham Ashton-Butt; Sophie Bennett; Robin J. Boyd; Ella Browning; Graeme Buchanan; Adam Fraser; Sian E. Green; Robert Hawkes; Becky E. Heath; Pen-Yuan Hsing; et al. (Environmental Management, 2026)

Host and Environmental Drivers of Gut Microbiome Variation in Wild Anolis Lizards - Yanileth F. López Tacoaman; Maria Alcivar; Karla Alujević; Leah Bakewell; John David Curlis; Anabarbara Gonzalez; Noah D. Gripshover; Samir Gulati; Renata M. Pirani; Noa Ratia; Daniel Romero; Kelly Lin Wuthrich; et al. (Molecular Ecology, 2026)
Animals maintain close associations with diverse microbiota that inhabit their digestive tracts, and these associations can profoundly affect host physiology and fitness. Gut microbiome composition is shaped by both host traits and environmental factors, yet the relative importance of these forces remains unclear in many taxa, including squamate reptiles (lizards and snakes). To address this gap, we analysed the gut microbiomes of seven species of Anolis lizards in the lowland tropical rainforest of central Panama. We sought to determine how environmental and host species characteristics shaped gut microbiome composition. Specifically, we examined (1) interspecific variation in the anole gut microbiome, (2) the relative roles of environment and host species in shaping gut microbiomes across two study locations, and (3) patterns of phylosymbiosis. We found that host‐related factors (species identity, body size, and phylogenetic distance) were significant predictors of the composition of Anolis gut microbiomes. However, environmental factors, including locality and year of sampling (associated with temperature, humidity, and precipitation), also exerted significant effects. We detected evidence of phylosymbiosis, but this pattern was moderate, possibly due to the strong effect of environmental variation. Our work contributes to the growing body of literature on lizard gut microbiomes by using comparative observations across habitats and species to identify the factors that shape these communities in the wild.

Levels of 129I in coastal Pacific Ocean waters from southern California, 2011–2020 and the legacy of Fukushima - A. J. Timothy Jull; Ching-Chih Chang; George S. Burr; Li Cheng; Joellen Russell; Mang Lin; Daniel R. Crocker; Mark Thiemens; Dana Biddulph; Marc W. Caffee; Tom Woodruff; Christopher Glynn; et al. (Frontiers in Marine Science, 2026)
The Fukushima Daiichi Nuclear Power Plant accident released radionuclides directly into the ocean as a result of the Great East Japan Earthquake on March 11, 2011. This material has been transported across the Pacific Ocean and detected in the northeastern Pacific. We began a surface ocean 129 I monitoring program a few months after this disaster in June 2011, with samples from Scripps Pier, La Jolla, California, USA, with the expectation that surface currents originating off the east coast of Japan could eventually carry radionuclides to the La Jolla site. We could not identify a significant distinct signal that can be traced to Fukushima from the record from 2011-2020. We have however recorded a systematic seasonal 129 I time series record that appears to be due to surface circulation variations along the California coast, or perhaps other unexplained effects. We have reported on some of these effects previously, where we summarized results up to 2018. Since then, we have analyzed additional samples obtained during our sampling program for 2018–2020 from Scripps and also report other results collected during 2015–2016 from Newport Beach, CA, which had not been reported. These results support and expand on the previously published dataset.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Contrasting behaviour in geogenic degassing along an active segment of the East Anatolian fault zone (Türkiye) - G. Yüce; W. D'Alessandro; C.C. Fu; F. Italiano; M. İçhedef; H. Elmacı; B. Kürkcüoğlu; B. Kahraman; A. Demirtaş; L.H. Lin; D. Yasin; Ş. Gürboğa; et al. (Applied Geochemistry, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Beyond temperature: predictive modelling of range shifts in benthic peracarids across the northern North Pacific under future climate scenarios - Stefanie Kaiser; Anna M. Jażdżewska; Sarah Gerken; Anne Helene S. Tandberg; Chih-Lin Wei; Davide Di Franco; Hanieh Saeedi; Hannah Owens; Henry Knauber; Emma Palacios Theil; Angelika Brandt; Pedro Martinez Arbizu; et al. (Progress in Oceanography, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Association between prenatal exposures to per- and polyfluoroalkyl substances and early language development in the ECHO cohort - Patricia Cintora; Lesliam Quirós-Alcalá; Adaeze W. Nzegwu; Sudhi Upadhyaya; Megan Woodbury; Sarah Dee Geiger; Rachel Morello-Frosch; Anne L. Dunlop; Theresa M. Bastain; Anne P. Starling; Dana Dabelea; Carlos A. Camargo; et al. (NeuroToxicology, 2025)

A new externally coupled, physically-based multi-model framework for simulating subsurface and overland flow hydrological processes on hillslopes - A T M Sakiur Rahman; Jiří Šimůnek; Scott A. Bradford; Hoori Ajami; Menberu B. Meles; Lin Chen; Adam Szymkiewicz; Mateusz Pawlowicz; Juan S. Acero Triana; Alberto Casillas-Trasvina; Sahila Beegum (Journal of Hydrology, 2025)

Meta-analysis on microplastics monitoring in global water resource recovery facilities: An emphasis on overlooked factors - Elinor S. Austin; Dana M. Austin; Linda Y. Tseng; Lin Liu; Zeth Kleinmeyer; Danielle Drake; Diego Rosso; Yian Sun (Environmental Pollution, 2025)

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Walruses are potentially exposed to paralytic shellfish toxin concentrations that impact their health during Alexandrium blooms in the Alaskan Arctic - Patrick Charapata; Evangeline Fachon; Donald M. Anderson; Gay Sheffield; Emily K. Bowers; Robert S. Pickart; Peigen Lin; Kathi A. Lefebvre (Harmful Algae, 2025)

Synergistic effects and mechanisms of ultrasonic, pH, and peracetic acid pretreatment on sludge anaerobic fermentation to stimulate short-chain fatty acid production - Eid S. Gaballah; Lei Gao; Richen Lin; Mahmoud M. Ali; Biao Yang; Mostafa Sobhi; Chongpeng Tang; Guangcan Zhu (Bioresource Technology, 2025)

Histopathological and immunohistochemical characterisation of inflammatory lesions in flying foxes naturally infected with Australian Bat Lyssavirus (ABLV). - Y. Lin Tan; M. Gimeno; P. Pinczowski; S. Gestier; E. Hall; M. Krockenberger (Journal of Comparative Pathology, 2025)

Mechanistic insights into cross-modal aroma-taste interactions mediating sweetness perception enhancement in Fu brick tea - Zhihui Hu; Amr M. Bakry; Lin Shi; Ping Zhan; Wanying He; Walaa A.M. Eid; Hussein Ferweez; Yahya S. Hamed; Hesham A. Ismail; Honglei Tian; Peng Wang (Food Chemistry, 2025)

Saxitoxin Linked to Deaths of Northern Fur Seals in the Southeast Bering Sea - Kathi A. Lefebvre; Chelsea M. Campbell; Lauren M. Divine; Paul Melovidov; Hanna Hellen; Kathy Burek Huntington; Emily K. Bowers; Natalie Rouse; Evangeline Fachon; Thomas J. Farrugia; Robert S. Pickart; Peigen Lin; et al. (Marine Mammal Science, 2025)
In August 2024, a northern fur seal mortality event was observed on St. Paul Island, AK in the southeast (SE) Bering Sea. Ten seals in good body condition were found dead along with large accumulations of dead fish on Benson Beach located on St. Paul Island. Full necropsies of the five available adult seals, one pup, and several fish did not reveal any overt causes of death. Testing of tissues for the algal neurotoxins domoic acid (DA) and saxitoxin (STX) confirmed the presence of STX in multiple tissues and physiological exposure in all five adult NFS and the two fish available for testing. DA was not detected in any samples. Complimentary samples of the SE Bering Sea ecosystem during the same time frame and location as the die off revealed bloom densities of Alexandrium catenella (the dinoflagellate that produces STX), large A. catenella cyst beds, and high prevalences of STX in fish (100%, n = 22), zooplankton (93%, n = 28), clams (100%, n = 10) and worms (93% n = 15) in the foraging area of NFS. High STX concentrations were observed in fish, clams, worms, and NFS urine, providing compelling evidence for a STX poisoning event.

Impact of U-10Mo HALEU fuel element tolerances on the Massachusetts Institute of Technology reactor safety and operational performance – Thermal hydraulics - Sero Yang; Valerio Mascolino; Laura M. Jamison; Kyle E. Anderson; Lin-wen Hu; Dhongik S. Yoon; John A. Stillman; Walid M. Mohamed; Erik H. Wilson (Annals of Nuclear Energy, 2025)

Impact of U-10Mo HALEU Fuel Element Tolerances on the Massachusetts Institute of Technology Reactor safety and operational performance – Neutronics - Valerio Mascolino; Sero Yang; Laura M. Jamison; Kyle E. Anderson; Lin-wen Hu; Dhongik S. Yoon; John A. Stillman; Walid Mohamed; Erik H. Wilson (Annals of Nuclear Energy, 2025)

Nicotinamide riboside combined with exercise to treat hypertension in middle-aged and older adults: a pilot randomized clinical trial - Yi Lin; Rola S. Zeidan; Stephanie Lapierre-Nguyen; Hannah M. Costello; Stephen D. Anton; Thomas W. Buford; Demetra D. Christou; Michelle L. Gumz; Christiaan Leeuwenburgh; Christopher R. Martens; Mary M. McDermott; Marie E. Migaud; et al. (GeroScience, 2025)
Aerobic exercise lowers blood pressure (BP) with varying effects in hypertensive adults, potentially due to age-related nicotinamide adenine dinucleotide (NAD) metabolism dysregulation. This pilot randomized clinical trial (RCT) tested the efficacy of combining aerobic exercise with the NAD booster nicotinamide riboside (NR) to enhance BP control. In this double-blinded RCT, 54 sedentary adults (≥ 55 years) with mean daytime systolic BP (SBP) ≥ 130 mmHg were randomized to 6 weeks of 1000 mg/day of NR combined with 3 days/week of supervised 30-min walking exercise (NR + Ex), Placebo combined with the same exercise regimen (PL + Ex), or NR alone (NR). The primary outcome was daytime SBP. Other outcomes included pulse wave velocity (PWV), NAD catabolites, and nighttime BP. The primary comparison was between NR + Ex and PL + Ex. Of 54 participants (mean age 67 years, 61% female), 49 (NR + Ex: n = 15, PL + Ex: n = 16, NR: n = 18) completed all study visits (93% adherence to exercise and 90% to supplementation). NR + Ex (mean change = 5.19 ± 13.2 mmHg) did not reduce SBP more than PL + Ex (− 2.71 ± 10.5 mmHg). NR + Ex (− 0.31 ± 0.77 m/s) showed a trend toward a greater reduction in PWV. Levels of NAD catabolites were higher in NR groups. In a post hoc analysis, NR + Ex showed a trend toward greater nighttime BP reductions (systolic: − 9.6 ± 9.22; diastolic: − 4.51 ± 7.12 mmHg) in participants without antihypertensive medications. NR + Ex was not superior to PL + Ex in reducing BP in hypertensive middle-aged and older. However, trends toward greater nighttime BP reduction in NR + Ex in participants without antihypertensive medication warrant further investigation in a Phase IIb RCT. Graphical Abstract

Status quo and predictions of the most and least discussed sustainable development goals - H.-H. Chung; F.-L. Chung; S.-M. Lin (International Journal of Environmental Science and Technology, 2025)

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Soil Carbon Saturation: What Do We Really Know? - Katerina Georgiou; Denis Angers; Ryan E. Champiny; M. Francesca Cotrufo; Matthew E. Craig; Sebastian Doetterl; A. Stuart Grandy; Jocelyn M. Lavallee; Yang Lin; Emanuele Lugato; Christopher Poeplau; Katherine S. Rocci; et al. (Global Change Biology, 2025)
Managing soils to increase organic carbon storage presents a potential opportunity to mitigate and adapt to global change challenges, while providing numerous co‐benefits and ecosystem services. However, soils differ widely in their potential for carbon sequestration, and knowledge of biophysical limits to carbon accumulation may aid in informing priority regions. Consequently, there is great interest in assessing whether soils exhibit a maximum capacity for storing organic carbon, particularly within organo–mineral associations given the finite nature of reactive minerals in a soil. While the concept of soil carbon saturation has existed for over 25 years, recent studies have argued for and against its importance. Here, we summarize the conceptual understanding of soil carbon saturation at both micro‐ and macro‐scales, define key terminology, and address common concerns and misconceptions. We review methods used to quantify soil carbon saturation, highlighting the theory and potential caveats of each approach. Critically, we explore the utility of the principles of soil carbon saturation for informing carbon accumulation, vulnerability to loss, and representations in process‐based models. We highlight key knowledge gaps and propose next steps for furthering our mechanistic understanding of soil carbon saturation and its implications for soil management.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Correction to: Do past and present abiotic conditions explain variation in the nutritional quality of wildflower pollens for bees? - Anthony D. Vaudo; Eva Lin; Jillian A. Luthy; Anne S. Leonard; Eliza M. Grames (Evolutionary Ecology, 2025)

Surgical Parameters During Reverse Shoulder Arthroplasty Predict Post-Surgical Kinematics During the Hand-to-Head Motion - Ajinkya A. Rai; Clarissa M. LeVasseur; Gillian E. Kane; Maria A. Munsch; Christopher J. Como; Alexandra S. Gabrielli; Jonathan D. Hughes; William J. Anderst; Albert Lin (Annals of Biomedical Engineering, 2025)

Challenges to and importance of considering early and intermediate ontogenetic stages in mangrove forest recovery and restoration - Taylor M. Sloey; Sean P. Charles; Lin Xiong; Edward Castañeda-Moya; Erik S. Yando; David Lagomasino (Marine Pollution Bulletin, 2024)

Analysis of contaminant residues in honey bee hive matrices - Donna A. Glinski; S. Thomas Purucker; Jeffrey M. Minucci; Rodney T. Richardson; Chia-Hua Lin; Reed M. Johnson; W. Matthew Henderson (Science of The Total Environment, 2024)

Do past and present abiotic conditions explain variation in the nutritional quality of wildflower pollens for bees? - Anthony D. Vaudo; Eva Lin; Jillian A. Luthy; Anne S. Leonard; Eliza M. Grames (Evolutionary Ecology, 2024)

Speciation, phytoavailability, and accumulation of toxic elements and sulfur by humic acid-fertilized lemongrass and common sage in a sandy soil treated with heavy oil fly ash: A trial for management of power stations wastes - Samir G. Al-Solaimani; Abdulrahman Al-Qureshi; Sherif S. Hindi; Omer H. Ibrahim; Magdi A.A. Mousa; Yen-Lin Cho; Noha E.E. Hassan; Yu-Ting Liu; Shan-Li Wang; Vasileios Antoniadis; Jörg Rinklebe; Sabry M. Shaheen (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Estimating ambient air pollutant concentrations outside and inside homes in the Subpopulations and Intermediate outcomes in COPD air pollution (SPIROMICS air) cohort - Kipruto Kirwa; Amanda J. Gassett; Coralynn Sack; Laura M. Paulin; Cheryl S. Pirozzi; R. Graham Barr; Prescott G. Woodruff; MeiLan Han; May-Lin Wilgus; Igor Barjaktarevic; Stephen Peters; Nadia N. Hansel; et al. (Environmental Research, 2024)

Residential Proximity to Metal-Emitting Industries and Toenail Metal Concentration in the US Gulf States - Joyce J. Y. Lin; Emily J. Werder; Kaitlyn G. Lawrence; W. Braxton Jackson; Dale P. Sandler; Aisha S. Dickerson; Lawrence S. Engel; Ana M. Rule (Exposure and Health, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Associations of a toenail metal mixture with attention and memory in the Gulf long-term follow-up (GuLF) study - Joyce J.Y. Lin; Jordan R. Kuiper; Aisha S. Dickerson; Jessie P. Buckley; Heather E. Volk; Diane S. Rohlman; Kaitlyn G. Lawrence; W. Braxton Jackson; Dale P. Sandler; Lawrence S. Engel; Ana M. Rule (Science of The Total Environment, 2024)

Investigating the partitioning behavior of per- and polyfluoroalkyl substances (PFAS) during thermal landfill leachate evaporation - Allison R. Cerlanek; Alina S. Timshina; Nicole Robey; Ashley M. Lin; Helena M. Solo-Gabriele; Timothy G. Townsend; John A. Bowden (Journal of Hazardous Materials, 2024)

Association between pre-diagnosis recreational physical activity and risk of breast cancer recurrence: the California Teachers Study - Dan Lin; Cheryl L. Thompson; Alaina Demalis; Rebecca Derbes; Laila Al-Shaar; Emma S. Spielfogel; Kathleen M. Sturgeon (Cancer Causes & Control, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

FDA-approved disulfiram as a novel treatment for aggressive leukemia - Mawar Karsa; Lin Xiao; Emma Ronca; Angelika Bongers; Dayna Spurling; Ayu Karsa; Sandra Cantilena; Anna Mariana; Tim W. Failes; Greg M. Arndt; Laurence C. Cheung; Rishi S. Kotecha; et al. (Journal of Molecular Medicine, 2024)
Acute leukemia continues to be a major cause of death from disease worldwide and current chemotherapeutic agents are associated with significant morbidity in survivors. While better and safer treatments for acute leukemia are urgently needed, standard drug development pipelines are lengthy and drug repurposing therefore provides a promising approach. Our previous evaluation of FDA-approved drugs for their antileukemic activity identified disulfiram, used for the treatment of alcoholism, as a candidate hit compound. This study assessed the biological effects of disulfiram on leukemia cells and evaluated its potential as a treatment strategy. We found that disulfiram inhibits the viability of a diverse panel of acute lymphoblastic and myeloid leukemia cell lines ( n = 16) and patient-derived xenograft cells from patients with poor outcome and treatment-resistant disease ( n = 15). The drug induced oxidative stress and apoptosis in leukemia cells within hours of treatment and was able to potentiate the effects of daunorubicin, etoposide, topotecan, cytarabine, and mitoxantrone chemotherapy. Upon combining disulfiram with auranofin, a drug approved for the treatment of rheumatoid arthritis that was previously shown to exert antileukemic effects, strong and consistent synergy was observed across a diverse panel of acute leukemia cell lines, the mechanism of which was based on enhanced ROS induction. Acute leukemia cells were more sensitive to the cytotoxic activity of disulfiram than solid cancer cell lines and non-malignant cells. While disulfiram is currently under investigation in clinical trials for solid cancers, this study provides evidence for the potential of disulfiram for acute leukemia treatment. Key messages Disulfiram induces rapid apoptosis in leukemia cells by boosting oxidative stress. Disulfiram inhibits leukemia cell growth more potently than solid cancer cell growth. Disulfiram can enhance the antileukemic efficacy of chemotherapies. Disulfiram strongly synergises with auranofin in killing acute leukemia cells by ROS induction. We propose testing of disulfiram in clinical trial for patients with acute leukemia.

Dynamic efficiency evaluation of electric power and environmental treatment efficiency in China - Y. Li; Y. Chiu; T.-Y. Lin; S.-M. Wang; T.-H. Chang (International Journal of Environmental Science and Technology, 2024)

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

Advancing ecological assessment of the Arabian Gulf through eDNA metabarcoding: opportunities, prospects, and challenges - Thadickal V. Joydas; Seerangan Manokaran; Jayanath Gopi; Jayachandran P. Rajakumar; Lin Yu-Jia; Moritz Heinle; Mazen K. Nazal; Karuppasamy P. Manikandan; Maryam Qashqari; Sowmya P. Mohandas; Syed A. Hussain; Rommel H. Maneja; et al. (Frontiers in Marine Science, 2024)
The Arabian Gulf (hereafter ‘the Gulf’) is renowned for its unique ecological characteristics and distinct marine life. It offers a diverse range of ecosystems that have adapted to the impacts posed by natural stress and human activities. Regular biomonitoring and diversity assessments are necessary to document the health of the Gulf ecosystem and to implement appropriate measures for effective conservation and management. Recently, environmental DNA (eDNA), a total pool of DNA isolated from environmental samples, has emerged as a highly effective tool for ecological studies. This review explores the opportunities, prospects, and challenges associated with employing eDNA metabarcoding in the ecological assessment and biomonitoring of the Gulf. It provides an overview of the status of the Gulf ecosystem and discusses the potential applications of eDNA metabarcoding in assessing biodiversity, monitoring invasive species, and evaluating ecosystem health. Additionally, the investigation addresses the challenges inherent in implementing this technique, considering environmental complexities, methodological intricacies, and data interpretation. Overall, this review emphasizes the immense potential of eDNA metabarcoding in advancing ecological assessment in the Gulf and calls for further research and collaboration to harness its benefits in this unique marine ecosystem.

Vegetation−fire feedbacks increase subtropical wildfire risk in scrubland and reduce it in forests - P. Wei; B. Lamont; T. He; W. Xue; P.C. Wang; W. Song; R. Zhang; A.B. Keyhani; S. Zhao; W. Lu; F. Dong; R. Gao; et al. (Journal of Environmental Management, 2024)

The Pacific water flow branches in the eastern Chukchi Sea - Robert S. Pickart; Peigen Lin; Frank Bahr; Leah T. McRaven; Jie Huang; Astrid Pacini; Kevin R. Arrigo; Carin J. Ashjian; Catherine Berchok; Mark F. Baumgartner; Kyoung-Ho Cho; Lee W. Cooper; et al. (Progress in Oceanography, 2023)

Promotion of the catalytic polymerization of hydroquinone towards humic-like substances by graphitic carbon nitride - M.M.M. Ahmed; Yu-Ting Liu; S. Venkatesan; Min Chien Wu; Howida M. Nail; Der-Lii M. Tzou; Ming-Chang Lin; Kai-Yue Chen; Yu-min Tzou (Journal of Environmental Chemical Engineering, 2023)

Emerging polycyclic aromatic hydrocarbon (PAH) and trace metal leachability from reclaimed asphalt pavement (RAP) - Ashley M. Lin; Alina S. Timshina; Jordan K. Magnuson; John A. Bowden; Timothy G. Townsend (Chemosphere, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Simulation of CO2 capture from natural gas by cyclic pressure swing adsorption process using activated carbon - Haitao Lin; Jianbo Lu; Azher M. Abed; Kaushik Nag; Mohamed Fayed; Ahmed Deifalla; Abdullah S. Bin Mahfouz; Ahmed M. Galal (Chemosphere, 2023)

Geological controls on the distribution of gas hydrates in the shallow parts of the gas hydrate stability zone – constraints from seafloor drilling off Taiwan - G. Bohrmann; C. Berndt; S. Lin; T.-H. Tu; A.T. Lin; H.-H. Hsu; M.-C. Lai; W.-C. Chi; C. Deusner; J. Elger; K. Wallmann; T. Freudenthal; et al. (Marine and Petroleum Geology, 2023)

Up in the air: Polyfluoroalkyl phosphate esters (PAPs) in airborne dust captured by air conditioning (AC) filters - Alina S. Timshina; William J. Sobczak; Emily K. Griffin; Ashley M. Lin; Timothy G. Townsend; John A. Bowden (Chemosphere, 2023)

Drought-vulnerable vegetation increases exposure of disadvantaged populations to heatwaves under global warming: A case study from Los Angeles - Chunyu Dong; Yu Yan; Jie Guo; Kairong Lin; Xiaohong Chen; Gregory S. Okin; Thomas W. Gillespie; Jake Dialesandro; Glen M. MacDonald (Sustainable Cities and Society, 2023)

Interactions between marine megafauna and plastic pollution in Southeast Asia - Lucy C.M. Omeyer; Emily M. Duncan; Neil Angelo S. Abreo; Jo Marie V. Acebes; Lea A. AngSinco-Jimenez; Sabiqah T. Anuar; Lemnuel V. Aragones; Gonzalo Araujo; Luis R. Carrasco; Marcus A.H. Chua; Muhammad R. Cordova; Lantun P. Dewanti; et al. (Science of The Total Environment, 2023)

Centenarian clocks: epigenetic clocks for validating claims of exceptional longevity - Eric Dec; James Clement; Kaiyang Cheng; George M. Church; Michael B. Fossel; David H. Rehkopf; Luis Rosero-Bixby; Michael S. Kobor; David TS. Lin; Ake T. Lu; Zhe Fei; Wei Guo; et al. (GeroScience, 2023)
Claims surrounding exceptional longevity are sometimes disputed or dismissed for lack of credible evidence. Here, we present three DNA methylation-based age estimators (epigenetic clocks) for verifying age claims of centenarians. The three centenarian clocks were developed based on n = 7039 blood and saliva samples from individuals older than 40, including n = 184 samples from centenarians, 122 samples from semi-supercentenarians (aged 105 +), and 25 samples from supercentenarians (aged 110 +). The oldest individual was 115 years old. Our most accurate centenarian clock resulted from applying a neural network model to a training set composed of individuals older than 40. An epigenome-wide association study of age in different age groups revealed that age effects in young individuals (age < 40) are correlated ( r = 0.55) with age effects in old individuals (age > 90). We present a chromatin state analysis of age effects in centenarians. The centenarian clocks are expected to be useful for validating claims surrounding exceptional old age.

A systematic evidence map for the evaluation of noncancer health effects and exposures to polychlorinated biphenyl mixtures - Laura M. Carlson; Krista Christensen; Sharon K. Sagiv; Pradeep Rajan; Carolyn R. Klocke; Pamela J. Lein; Evan Coffman; Rachel M. Shaffer; Erin E. Yost; Xabier Arzuaga; Pam Factor-Litvak; Alexander Sergeev; et al. (Environmental Research, 2023)

Pyrolysis and Gasification Characteristics of Galdieria sulphuraria Microalgae - Fateme Banihashemi; Amr F. M. Ibrahim; Shuguang Deng; Jerry Y. S. Lin (BioEnergy Research, 2023)

Soil organic carbon, aggregation and fungi community after 44 years of no-till and cropping systems in the Central Great Plains, USA - James S. Lin; Marcos V. M. Sarto; Tiffany L. Carter; Dallas E. Peterson; Colleen Gura; Laura Mino; Megan Rohrs; Hallie Lucas; Jamie Clark; Charles W. Rice (Archives of Microbiology, 2023)

The role of copper crystallization and segregation toward enhanced methanol synthesis via CO2 hydrogenation over CuZrO2 catalysts: A combined experimental and computational study - Francielle C.F. Marcos; Raphael S. Alvim; Lili Lin; Luis E. Betancourt; Davi D. Petrolini; Sanjaya D. Senanayake; Rita M.B. Alves; José M. Assaf; Jose A. Rodriguez; Reinaldo Giudici; Elisabete M. Assaf (Chemical Engineering Journal, 2023)

Elastoplastic Modelling of Porous Limestones with Porosity Dependency - B. Han; Q. M. Gong; X. L. Du; Y. Gao; W. Q. Shen; S. Lin (Rock Mechanics and Rock Engineering, 2022)

A comprehensive review on water stable metal-organic frameworks for large-scale preparation and applications in water quality management based on surveys made since 2015 - R. Y. Li; Z. S. Wang; Z. Y. Yuan; Constance Van Horne; Viatcheslav Freger; M. Lin; R. K. Cai; J. P. Chen (Critical Reviews in Environmental Science and Technology, 2022)

Registered clinical trials investigating treatment of long COVID: a scoping review and recommendations for research - Felicia Ceban; Alexia Leber; Muhammad Youshay Jawad; Mathew Yu; Leanna M. W. Lui; Mehala Subramaniapillai; Joshua D. Di Vincenzo; Hartej Gill; Nelson B. Rodrigues; Bing Cao; Yena Lee; Kangguang Lin; et al. (Infectious Diseases, 2022)

Factors associated with changes in exercise behaviors during the COVID-19 pandemic - Caroline Himbert; Cassandra A. Hathaway; Bailee Daniels; Karen Salas; Anjelica Ashworth; Biljana Gigic; Tengda Lin; Richard Viskochil; Anne C. Kirchhoff; Douglas Grossman; Jennifer Ose; Jonathan Tward; et al. (Cancer Causes & Control, 2022)

A bibliometric review of peripartum cardiomyopathy compared to other cardiomyopathies using artificial intelligence and machine learning - M. Grosser; H. Lin; M. Wu; Y. Zhang; S. Tipper; D. Venter; J. Lu; C. G. dos Remedios (Biophysical Reviews, 2022)

Determining tolerance levels for quality assurance of 3D printed bolus for modulated arc radiotherapy of the nose - T. Kairn; S. Talkhani; P. H. Charles; B. Chua; C. Y. Lin; A. G. Livingstone; S. K. Maxwell; T. Poroa; E. Simpson-Page; E. Spelleken; M. Vo; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2021)

Antigen production and development of an indirect ELISA based on the nucleocapsid protein to detect human SARS-CoV-2 seroconversion - Marcelo S. Conzentino; Karl Forchhammer; Emanuel M. Souza; Fábio O. Pedrosa; Meri B. Nogueira; Sônia M. Raboni; Fabiane G. M. Rego; Dalila L. Zanette; Mateus N. Aoki; Jeanine M. Nardin; Bruna Fornazari; Hugo M. P. Morales; et al. (Brazilian Journal of Microbiology, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Low diversity of a key phytoplankton group along the West Antarctic Peninsula - Michael S. Brown; Jeff S. Bowman; Yajuan Lin; Colette J. Feehan; Carly M. Moreno; Nicolas Cassar; Adrian Marchetti; Oscar M. Schofield (Limnology and Oceanography, 2021)
The West Antarctic Peninsula (henceforth “Peninsula”) is experiencing rapid warming and melting that is impacting the regional marine food web. The primary phytoplankton groups along the Peninsula are diatoms and cryptophytes. Relative to diatoms, there has been little focus on regional cryptophytes, and thus our understanding of their diversity and ecology is limited, especially at the species level. This gap is important, as diatoms and cryptophytes play distinct roles in the regional marine food web and biogeochemistry. Here, we use a phylogenetic placement approach with 18S rRNA gene amplicon sequence variants to assess surface ocean cryptophyte diversity and its drivers at a high taxonomic resolution along the Peninsula. Data were collected over 5 years (2012–2016) during the regional research cruises of the Palmer Long‐Term Ecological Research program. Our results indicate that there are two major cryptophyte taxa along the Peninsula, consisting of distinct Geminigera spp., which in aggregate always comprise nearly 100% of the cryptophyte community (indicating low taxa evenness). The primary taxon dominates the cryptophyte community across all samples/years, which span a broad range of oceanographic conditions. A shift in cryptophyte community composition between a lower (higher) primary (secondary) taxon percentage is associated with distinct oceanographic conditions, including lower (higher) temperature, salinity, nutrients, and cryptophyte relative abundance (phytoplankton biomass and diatom relative abundance). These results emphasize the need for a full characterization of the ecology of these two taxa, as it is predicted that cryptophytes will increase along the Peninsula given projections of continued regional environmental change.

From zero to infinity: Minimum to maximum diversity of the planet by spatio‐parametric Rao’s quadratic entropy - Duccio Rocchini; Matteo Marcantonio; Daniele Da Re; Giovanni Bacaro; Enrico Feoli; Giles M. Foody; Reinhard Furrer; Ryan J. Harrigan; David Kleijn; Martina Iannacito; Jonathan Lenoir; Meixi Lin; et al. (Global Ecology and Biogeography, 2021)
Aim The majority of work done to gather information on the Earth's biodiversity has been carried out using in‐situ data, with known issues related to epistemology (e.g., species determination and taxonomy), spatial uncertainty, logistics (time and costs), among others. An alternative way to gather information about spatial ecosystem variability is the use of satellite remote sensing. It works as a powerful tool for attaining rapid and standardized information. Several metrics used to calculate remotely sensed diversity of ecosystems are based on Shannon’s information theory, namely on the differences in relative abundance of pixel reflectances in a certain area. Additional metrics like the Rao’s quadratic entropy allow the use of spectral distance beside abundance, but they are point descriptors of diversity, that is they can account only for a part of the whole diversity continuum. The aim of this paper is thus to generalize the Rao’s quadratic entropy by proposing its parameterization for the first time. Innovation The parametric Rao’s quadratic entropy, coded in R, (a) allows the representation of the whole continuum of potential diversity indices in one formula, and (b) starting from the Rao’s quadratic entropy, allows the explicit use of distances among pixel reflectance values, together with relative abundances. Main conclusions The proposed unifying measure is an integration between abundance‐ and distance‐based algorithms to map the continuum of diversity given a satellite image at any spatial scale. Being part of the rasterdiv R package, the proposed method is expected to ensure high robustness and reproducibility.

A global collaboration to study intimate partner violence-related head trauma: The ENIGMA consortium IPV working group - Carrie Esopenko; Jessica Meyer; Elisabeth A. Wilde; Amy D. Marshall; David F. Tate; Alexander P. Lin; Inga K. Koerte; Kimberly B. Werner; Emily L. Dennis; Ashley L. Ware; Nicola L. de Souza; Deleene S. Menefee; et al. (Brain Imaging and Behavior, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

The influence of vector‐borne disease on human history: socio‐ecological mechanisms - Tejas S. Athni; Marta S. Shocket; Lisa I. Couper; Nicole Nova; Iain R. Caldwell; Jamie M. Caldwell; Jasmine N. Childress; Marissa L. Childs; Giulio A. De Leo; Devin G. Kirk; Andrew J. MacDonald; Kathryn Olivarius; et al. (Ecology Letters, 2021)
Vector‐borne diseases (VBDs) are embedded within complex socio‐ecological systems. While research has traditionally focused on the direct effects of VBDs on human morbidity and mortality, it is increasingly clear that their impacts are much more pervasive. VBDs are dynamically linked to feedbacks between environmental conditions, vector ecology, disease burden, and societal responses that drive transmission. As a result, VBDs have had profound influence on human history. Mechanisms include: (1) killing or debilitating large numbers of people, with demographic and population‐level impacts; (2) differentially affecting populations based on prior history of disease exposure, immunity, and resistance; (3) being weaponised to promote or justify hierarchies of power, colonialism, racism, classism and sexism; (4) catalysing changes in ideas, institutions, infrastructure, technologies and social practices in efforts to control disease outbreaks; and (5) changing human relationships with the land and environment. We use historical and archaeological evidence interpreted through an ecological lens to illustrate how VBDs have shaped society and culture, focusing on case studies from four pertinent VBDs: plague, malaria, yellow fever and trypanosomiasis. By comparing across diseases, time periods and geographies, we highlight the enormous scope and variety of mechanisms by which VBDs have influenced human history.

Characterization and validation of QTLs for adult plant stripe rust resistance in Chinese wheat landrace Dabaimai - M. Y. Wang; M. R. Xu; F. T. Wang; S. J. A. Shah; J. Feng; R. M. Lin; S. C. Xu (Cereal Research Communications, 2021)

Machine learning prediction of neurocognitive impairment among people with HIV using clinical and multimodal magnetic resonance imaging data - Yunan Xu; Yizi Lin; Ryan P. Bell; Sheri L. Towe; John M. Pearson; Tauseef Nadeem; Cliburn Chan; Christina S. Meade (Journal of NeuroVirology, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Regional drivers of diversification in the late Quaternary in a widely distributed generalist species, the common pheasant Phasianus colchicus - Simin Liu; Yang Liu; Edouard Jelen; Mansour Alibadian; Cheng‐Te Yao; Xintong Li; Nasrin Kayvanfar; Yutao Wang; Farhad S. M. Vahidi; Jian‐Lin Han; Gombobaatar Sundev; Zhengwang Zhang; et al. (Journal of Biogeography, 2020)
Aim Pleistocene climate and associated environmental changes have influenced phylogeographic patterns of many species. These not only depend on a species’ life history but also vary regionally. Consequently, populations of widespread species that occur in several biomes might display different evolutionary trajectories. We aimed to identify regional drivers of diversification in the common pheasant, a widely distributed ecological generalist. Location Asia. Taxon Common pheasant Phasianus colchicus . Methods Using a comprehensive geographical sampling of 204 individuals from the species’ entire range genotyped at seven nuclear and two mitochondrial loci, we reconstructed spatio‐temporal diversification and demographic history of the common pheasant. We applied Bayesian phylogenetic inference to describe phylogeographic structure, generated a species tree and inferred demographic history within and migration between lineages. Moreover, to establish a taxonomic framework, we conducted a species delimitation analysis. Results The common pheasant diversified during the Late Pleistocene into eight distinct lineages. It originated at the edge of the Qinghai–Tibetan plateau and spread to East and Central Asia. Only the widely distributed lowland lineage of East Asia displayed recent range expansion. Greater phylogeographic structure was identified elsewhere, with lineages showing no sign of recent demographic changes. One lineage in south‐central China is the result of long‐term isolation within a climatically stable but topographically complex region. In lineages from arid Central Asia and China, range expansions were impeded by repeated population fragmentation during dry glacial periods and by recent aridification. Main conclusions Spatio‐temporal phylogeographic frameworks of widespread taxa such as the common pheasant provide valuable opportunities to identify divergent drivers of regional diversification. Our results suggest that diversification and population histories in the eight distinct evolutionary lineages were shaped by regionally variable effects of past climate and associated environmental changes. The evolutionary history of the common pheasant is best reflected by its being split into three species.

Advanced psychometric testing on a clinical screening tool to evaluate insomnia: sleep condition indicator in patients with advanced cancer - Chung-Ying Lin; Andy S. K. Cheng; Vida Imani; Mohsen Saffari; Maurice M. Ohayon; Amir H. Pakpour (Sleep and Biological Rhythms, 2020)
Purpose To examine the psychometric properties of the Sleep Condition Indicator (SCI) using different psychometric approaches [including classical test theory, Rasch models, and receiver operating characteristics (ROC) curve] among patients with advanced cancer. Methods Through convenience sampling, patients with cancer at stage III or IV ( n = 859; 511 males; mean ± SD age = 67.4 ± 7.5 years) were recruited from several oncology units of university hospitals in Iran. All the participants completed the SCI, Insomnia Severity Index (ISI), Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), Hospital Anxiety and Depression Scale (HADS), General Health Questionnaire (GHQ), and Edmonton Symptom Assessment Scale (ESAS). In addition, 491 participants wore an actigraph device to capture objective sleep. Results Classical test theory [factor loadings from confirmatory factor analysis = 0.76–0.89; test–retest reliability = 0.80–0.93] and Rasch analysis [infit mean square (MnSq) = 0.63–1.31; outfit MnSq = 0.61–1.23] both support the construct validity of the SCI. The SCI had significant associations with ISI, PSQI, ESS, HADS, GHQ, and ESAS. In addition, the SCI has satisfactory area under ROC curve (0.92) when comparing a gold standard of insomnia diagnosis. Significant differences in the actigraphy measure were found between insomniacs and non-insomniacs based on the SCI score defined by ROC. Conclusion With the promising psychometric properties shown in the SCI, healthcare providers can use this simple assessment tool to target the patients with advanced cancer who are at risk of insomnia and subsequently provide personalized care efficiently.

Peripheral ProBDNF Delivered by an AAV Vector to the Muscle Triggers Depression-Like Behaviours in Mice - L. Y. Lin; S. Kelliny; L. C. Liu; M. Al-Hawwas; X. F. Zhou; L. Bobrovskaya (Neurotoxicity Research, 2020)

A System Level Analysis of Coastal Ecosystem Responses to Hurricane Impacts - C. J. Patrick; L. Yeager; A. R. Armitage; F. Carvallo; V. M. Congdon; K. H. Dunton; M. Fisher; A. K. Hardison; J. D. Hogan; J. Hosen; X. Hu; B. Kiel Reese; et al. (Estuaries and Coasts, 2020)

A Major Hydrothermal Reservoir Underneath the Tatun Volcano Group of Taiwan: Clues from a Dense Linear Geophone Array - C. H. Lin; Y. C. Lai; M. H. Shih; C. J. Lin; J. S. Ku; Y. C. Huang (Pure and Applied Geophysics, 2020)
A dense linear geophone array is deployed across the Tatun volcano group (TVG) at the northern tip of Taiwan, where more than 7 million residents live in the Taipei metropolis. The array is composed of 50 geophones with a station spacing of ~ 200 m in average, and it is designed for striking in the NW–SE direction to record the many earthquakes in eastern Taiwan, where the Philippine Sea plate subducted beneath the Eurasia plate. The detailed examination of felt earthquakes shows consistent P-wave delays are recorded at particular stations of the array. The further forward modeling indicates there is a low-velocity zone (LVZ) at depths between ~ 0.5 and ~ 2.5 km beneath the major fumarole sites. Combining this preliminary result with previous studies including clustering seismicity, volcanic earthquakes, low-resistivity zone, strong degassing processes and shallow velocity structures, we suggest that the LVZ might be associated with the major hydrothermal reservoir at the TVG. The identification of the hydrothermal reservoir by the LVZ not only implies a potential volcanic threat, such as phreatic eruptions, in the future, but also provides the possibility of sustainable geothermal resources for replacing traditional nuclear and fossil fuel power plants. Detailed images of the LVZ and other volcanic structures will be obtained soon when dense geophone arrays with more than 600 geophones are deployed from 2020 to 2022.

DNA methylation and histone acetylation changes to cytochrome P450 2E1 regulation in normal aging and impact on rates of drug metabolism in the liver - Mohamad M. Kronfol; Fay M. Jahr; Mikhail G. Dozmorov; Palak S. Phansalkar; Lin Y. Xie; Karolina A. Aberg; MaryPeace McRae; Elvin T. Price; Patricia W. Slattum; Philip M. Gerk; Joseph L. McClay (GeroScience, 2020)

Non-Invasive Quantification of Ventricular Contractility, Arterial Elastic Function and Ventriculo-Arterial Coupling from a Single Diagnostic Encounter Using Simultaneous Arterial Tonometry and Magnetic Resonance Imaging - Mayooran Namasivayam; Audrey Adji; Linda Lin; Christopher S. Hayward; Michael P. Feneley; Michael F. O’Rourke; David W. M. Muller; Andrew Jabbour (Cardiovascular Engineering and Technology, 2020)

A deep-level region-based visual representation architecture for detecting strawberry flowers in an outdoor field - P. Lin; W. S. Lee; Y. M. Chen; N. Peres; C. Fraisse (Precision Agriculture, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Effect of Peptide AEDG on Telomere Length and Mitotic Index of PHA-Stimulated Human Blood Lymphocytes - V. Kh. Khavinson; A. A. Pendina; O. A. Efimova; A. V. Tikhonov; A. S. Koltsova; M. I. Krapivin; A. V. Petrovskaia-Kaminskaia; L. I. Petrova; N. S. Lin’kova; V. S. Baranov (Bulletin of Experimental Biology and Medicine, 2019)

Crops For the Future (CFF): an overview of research efforts in the adoption of underutilised species - Peter J. Gregory; Sean Mayes; Chai Hui Hui; Ebrahim Jahanshiri; Advina Julkifle; Giva Kuppusamy; Ho Wai Kuan; Tan Xin Lin; Festo Massawe; T. A. S. T. M. Suhairi; Sayed N. Azam-Ali (Planta, 2019)

The Long-Term Effects of Ethanol and Corticosterone on the Mood-Related Behaviours and the Balance Between Mature BDNF and proBDNF in Mice - L. Y. Lin; S. Y. Luo; M. Al-Hawwas; M. F. Herselman; X. F. Zhou; Larisa Bobrovskaya (Journal of Molecular Neuroscience, 2019)

ARID1A, Prostaglandin E2, and Its Receptor as Possible Predictors of Malignant Transformation of the Endometrium in Endometriosis - A. S. Dyatlova; N. S. Lin’kova; V. O. Polyakova; N. G. Samoshkin; I. M. Kvetnoi (Bulletin of Experimental Biology and Medicine, 2019)

Ocean Climate Observing Requirements in Support of Climate Research and Climate Information - Detlef Stammer; Annalisa Bracco; Krishna AchutaRao; Lisa Beal; Nathaniel L. Bindoff; Pascale Braconnot; Wenju Cai; Dake Chen; Matthew Collins; Gokhan Danabasoglu; Boris Dewitte; Riccardo Farneti; et al. (Frontiers in Marine Science, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

The return of the frogs: The importance of habitat refugia in maintaining diversity during a disease outbreak - Donald T. McKnight; Monal M. Lal; Deborah S. Bower; Lin Schwarzkopf; Ross A. Alford; Kyall R. Zenger (Molecular Ecology, 2019)
Recent decades have seen the emergence and spread of numerous infectious diseases, often with severe negative consequences for wildlife populations. Nevertheless, many populations survive the initial outbreaks, and even undergo recoveries. Unfortunately, the long‐term effects of these outbreaks on host population genetics are poorly understood; to increase this understanding, we examined the population genetics of two species of rainforest frogs ( Litoria nannotis and Litoria serrata ) that have largely recovered from a chytridiomycosis outbreak at two national parks in the Wet Tropics of northern Australia. At the wetter, northern park there was little evidence of decreased genetic diversity in either species, and all of the sampled sites had high minor allele frequencies (mean MAF = 0.230–0.235), high heterozygosity (0.318–0.325), and few monomorphic markers (1.4%–4.0%); however, some recovered L. nannotis populations had low N e values (59.3–683.8) compared to populations that did not decline during the outbreak (1,537.4–1,756.5). At the drier, southern park, both species exhibited lower diversity (mean MAF = 0.084–0.180; heterozygosity = 0.126–0.257; monomorphic markers = 3.7%–43.5%; N e = 18.4–676.1). The diversity patterns in this park matched habitat patterns, with both species having higher diversity levels and fewer closely related individuals at sites with higher quality habitat. These patterns were more pronounced for L. nannotis, which has lower dispersal rates than L. serrata . These results suggest that refugia with high quality habitat are important for retaining genetic diversity during disease outbreaks, and that gene flow following disease outbreaks is important for re‐establishing diversity in populations where it was reduced.

Skin Fibroblasts as the Object for Clinical Diagnosis of Parkinson’s Disease in Persons of Different Ages - V. A. Zuev; A. S. Dyatlova; N. S. Lin’kova; I. M. Kvetnoi; N. N. Belushkina; V. A. Pal’tsev (Bulletin of Experimental Biology and Medicine, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

What Promotes the Recovery of Salt Marsh Infauna After Oil Spills? - J. W. Fleeger; M. R. Riggio; I. A. Mendelssohn; Q. Lin; D. R. Deis; D. S. Johnson; K. R. Carman; S. A. Graham; S. Zengel; A. Hou (Estuaries and Coasts, 2019)

Unidirectional monosynaptic connections from auditory areas to the primary visual cortex in the marmoset monkey - Piotr Majka; Marcello G. P. Rosa; Shi Bai; Jonathan M. Chan; Bing-Xing Huo; Natalia Jermakow; Meng K. Lin; Yeonsook S. Takahashi; Ianina H. Wolkowicz; Katrina H. Worthy; Ramesh Rajan; David H. Reser; et al. (Brain Structure and Function, 2019)

Black race and distant recurrence after neoadjuvant or adjuvant chemotherapy in breast cancer - Jessica M. Pastoriza; George S. Karagiannis; Juan Lin; Sonali Lanjewar; David Entenberg; John S. Condeelis; Joseph A. Sparano; Xiaonan Xue; Thomas E. Rohan; Maja H. Oktay (Clinical & Experimental Metastasis, 2018)

Aeromonas shuberti as a cause of multi‐organ necrosis in internal organs of Nile tilapia, Oreochromis niloticus - C Liu; O Q Chang; D F Zhang; K B Li; F Wang; M H Lin; C B Shi; L Jiang; Q Wang; S M Bergmann (Journal of Fish Diseases, 2018)
A disease with white spots in internal organs of Nile tilapia occurred in Zhanjiang, southern China. Multiple, white nodules, 0.8–2.2 mm in diameter, were scattered throughout the liver, spleen and kidney of diseased fish. Signs of nodules reproduced after artificial infection with the isolated strain. Isolated bacteria were Gram‐negative, facultative anaerobic, motile, short rod‐shaped, with a length of 1.2–2.2 μm. Morphological and biochemical tests, as well as phylogenetic analysis, all strongly indicated that the isolate from tilapia is identical to Aeromonas schubertii ( A. schubertii) which temporary named LF 1708 strain. Antibiotic sensitivity assays showed the LF 1708 is sensitive to 24 of 27 tested antibiotics. Pathogenicity test revealed that the isolate at the dose of 3.75 × 10 6 CFU /g killed 100% of experimental tilapia within 2 days and the dose of 1 × 10 7 CFU /g killed 100% of experimental zebrafish within 1 day. Histopathology of diseased tilapia infected with A. schubertii showed numerous necrotic lesions widely distributed in spleen, liver and kidney, and infiltration with a large number of bacteria. To our knowledge, this was the first report that associated A. schubertii with mortality in tilapia.

A Comparative Placebo-Controlled Clinical Trial of the Efficacy and Safety of Interferon β-1a Formulations for S.C. Administration in Patients with Remitting Multiple Sclerosis: First-Year Results - A. N. Boiko; L. P. Bosenko; V. V. Vasilovskii; L. I. Volkova; M. N. Zakharova; S. V. Kotov; E. V. Lekomtseva; T. I. Negrich; E. V. Parshina; O. P. Patrusheva; S. V. Prokopenko; D. V. Sazonov; et al. (Neuroscience and Behavioral Physiology, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

DNA Barcoding for Identification of Sugarcane Borers in China - J- D Wang; W- Z Wang; Z- L Lin; A Ali; H- Y Fu; M- T Huang; S- J Gao; R Wang (Neotropical Entomology, 2018)

Trade-offs between defence and competition in gregarious juvenile fluted giant clams (Tridacna squamosa L.) - Darren Z. H. Sim; Mei Lin Neo; Ambert C. F. Ang; Lynette S. M. Ying; Peter A. Todd (Marine Biology, 2018)

Temporal Profile and Severity Correlation of a Panel of Rat Spinal Cord Injury Protein Biomarkers - Zhihui Yang; Helen M. Bramlett; Ahmed Moghieb; Dongnan Yu; Ping Wang; Fan Lin; Carl Bauer; Tyler M. Selig; Emily Jaalouk; Amanda S. Weissman; Disa S. Rathore; Pammela Romo; et al. (Molecular Neurobiology, 2018)

Matrix Metalloproteinases MMP-1 and MMP-9 and Their Inhibitor TIMP-1 as Markers of Dilated Cardiomyopathy in Patients of Different Age - I. B. Antonov; K. L. Kozlov; E. M. Pal’tseva; O. V. Polyakova; N. S. Lin’kova (Bulletin of Experimental Biology and Medicine, 2018)

Role of LIF Cytokine and CD34 Angiogenesis Marker in Non-Developing Pregnancy - E. S. Popravka; A. S. Dyatlova; N. S. Lin’kova; Yu. S. Krylova; V. O. Polyakova; I. M. Kvetnoi (Bulletin of Experimental Biology and Medicine, 2017)

Development of a two-stage washing and biodegradation system to remediate octachlorinated dibenzo-p-dioxin-contaminated soils - J. L. Lin; C. D. Dong; C. W. Chen; S. H. Chen; T. E. Hsieh; C. M. Kao (International Journal of Environmental Science and Technology, 2017)

Formation of chlorite rims and the impact of pore-lining chlorite on reservoir quality: a case study from Shiqianfeng sandstones in upper Permian of Dongpu Depression, Bohai Bay Basin, eastern China - P. J. Ma; C. Y. Lin; S. Q. Zhang; C. M. Dong; Y. F. Xu (Australian Journal of Earth Sciences, 2017)

Evolution of landslide hotspots in Taiwan - S. C. Lin; M. C. Ke; C. M. Lo (Landslides, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Analysis of tandem repeat units of the promoter of capsanthin/capsorubin synthase (Ccs) gene in pepper fruit - Shi-Lin Tian; Zheng Li; Li Li; S. N. M. Shah; Zhen-Hui Gong (Physiology and Molecular Biology of Plants, 2017)

Cardiotoxicity Associated with Nicotinamide Phosphoribosyltransferase Inhibitors in Rodents and in Rat and Human-Derived Cells Lines - D. L. Misner; M. A. Kauss; J. Singh; H. Uppal; A. Bruening-Wright; B. M. Liederer; T. Lin; B. McCray; N. La; T. Nguyen; D. Sampath; P. S. Dragovich; et al. (Cardiovascular Toxicology, 2017)

Gonorrhea infection increases the risk of prostate cancer in Asian population: a nationwide population-based cohort study - Y.-C. Wang; C.-H. Chung; J.-H. Chen; M.-H. Chiang; Ti-Yin; C.-H. Tsao; F.-H. Lin; W.-C. Chien; S.-T. Shang; F.-Y. Chang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Variability of hydrological extreme events in East Asia and their dynamical control: a comparison between observations and two high-resolution global climate models - N. Freychet; A. Duchez; C.-H. Wu; C.-A. Chen; H.-H. Hsu; J. Hirschi; A. Forryan; B. Sinha; A. L. New; T. Graham; M. B. Andrews; C.-Y. Tu; et al. (Climate Dynamics, 2017)

Angiopoietins as serum biomarkers for lymphatic anomalies - Timothy D. Le Cras; Paula S. Mobberley-Schuman; Mary Broering; Lin Fei; Cameron C. Trenor; Denise M. Adams (Angiogenesis, 2017)

Changes in Sulforaphane and Selenocysteine Methyltransferase Transcript Levels in Broccoli Treated with Sodium Selenite - K. Huang; J. C. Lin; Q. Y. Wu; J. Y. Yan; M. Y. Liu; S. Zhang; W. J. Xiao (Plant Molecular Biology Reporter, 2016)

Changes in Sympathetic Innervation of Rat Caudal Artery in Experimental Myocardial Infarction. Effect of Semax Peptide - A. M. Gorbacheva; A. B. Berdalin; A. N. Stulova; A. D. Nikogosova; M. D. Lin; S. V. Buravkov; S. A. Gavrilova; V. B. Koshelev (Bulletin of Experimental Biology and Medicine, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Functional Genomic Analysis of the Impact of Camelina (Camelina sativa) Meal on Atlantic Salmon (Salmo salar) Distal Intestine Gene Expression and Physiology - Tyler D. Brown; Tiago S. Hori; Xi Xue; Chang Lin Ye; Derek M. Anderson; Matthew L. Rise (Marine Biotechnology, 2016)

Peptide Regulation of Skin Fibroblast Functions during Their Aging In Vitro - N. S. Lin’kova; A. O. Drobintseva; O. A. Orlova; E. P. Kuznetsova; V. O. Polyakova; I. M. Kvetnoy; V. Kh. Khavinson (Bulletin of Experimental Biology and Medicine, 2016)

Validation of self-reported comorbidity status of breast cancer patients with medical records: the California Breast Cancer Survivorship Consortium (CBCSC) - Cheryl Vigen; Marilyn L. Kwan; Esther M. John; Scarlett Lin Gomez; Theresa H. M. Keegan; Yani Lu; Salma Shariff-Marco; Kristine R. Monroe; Allison W. Kurian; Iona Cheng; Bette J. Caan; Valerie S. Lee; et al. (Cancer Causes & Control, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Drought tolerance as a driver of tropical forest assembly: resolving spatial signatures for multiple processes - M. K. Bartlett; Y. Zhang; J. Yang; N. Kreidler; S.‐W. Sun; L. Lin; Y.‐H. Hu; K.‐F. Cao; L. Sack (Ecology, 2016)
Spatial patterns in trait variation reflect underlying community assembly processes, allowing us to test hypotheses about their trait and environmental drivers by identifying the strongest correlates of characteristic spatial patterns. For 43 evergreen tree species (>1 cm dbh) in a 20‐ha seasonal tropical rainforest plot in Xishuangbanna, China, we compared the ability of drought‐tolerance traits, other physiological traits, and commonly measured functional traits to predict the spatial patterns expected from the assembly processes of habitat associations, niche‐overlap‐based competition, and hierarchical competition. We distinguished the neighborhood‐scale (0–20 m) patterns expected from competition from larger‐scale habitat associations with a wavelet method. Species’ drought tolerance and habitat variables related to soil water supply were strong drivers of habitat associations, and drought tolerance showed a significant spatial signal for influencing competition. Overall, the traits most strongly associated with habitat, as quantified using multivariate models, were leaf density, leaf turgor loss point (π tlp ; also known as the leaf wilting point), and stem hydraulic conductivity ( r 2 range for the best fit models = 0.27–0.36). At neighborhood scales, species spatial associations were positively correlated with similarity in π tlp , consistent with predictions for hierarchical competition. Although the correlation between π tlp and interspecific spatial associations was weak ( r 2

Soil Nitrous oxide and Carbon dioxide emissions following incorporation of above- and below-ground biomass of green bean - M. Shaaban; Q. Peng; R. Hu; S. Lin; J. Zhao (International Journal of Environmental Science and Technology, 2016)

Two New Species of the Genus Criotettix Bolivar (Orthoptera: Tetrigidae), with a Key to the Species of the Genus from China - W A Deng; Z M Zheng; S Z Wei; M P Lin; L L Lin (Neotropical Entomology, 2015)

The influence of shelf-sea fronts on winter monsoon over East China Sea - L.-Y. Oey; M.-C. Chang; S.-M. Huang; Y.-C. Lin; M.-A. Lee (Climate Dynamics, 2015)

Identification of a novel cyprinid herpesvirus 3 genotype detected in koi from the East Asian and South‐East Asian Regions - J Chen; D Chee; Y Wang; G Y Lim; S M Chong; Y N Lin; T Huangfu (Journal of Fish Diseases, 2015)
Cyprinid herpesvirus 3 (Cy HV ‐3) is a highly contagious virus that causes significant morbidity and mortality in common carp Cyprinus carpio L. and considered to be one of the most important pathogens of koi and common carp worldwide. Cyprinid herpesvirus 3 infected consignments imported from East Asian and South‐East Asian regions were identified during quarantine period in Singapore, and virus from a 2005 consignment was successfully isolated in koi fin cells. A combination of sequence analyses and duplex PCR were used to characterize 15 Cy HV ‐3 isolates detected in koi consignments between 2005 and 2011. Sequence analyses of the enlarged 9/5, SphI‐5 and TK gene regions identified both the Asian 1 ( n = 11) and European 4 ( n = 4) genotypes. Duplex PCR analysis of two variable marker regions between ORF 29 and ORF 30 (marker I) as well as ORF 133 and its upstream region (marker II ) revealed viruses of genotypes J (I ++ II + ), U/I (I −− II − ), an intermediate genotype (I ++ II − ) and a novel genotype, I ++ II +Δ , which was identified in viruses from seven different consignments. This novel genotype has a 13‐bp deletion in marker II , while maintaining the I ++ allele of marker I. The I ++ II +Δ genotype may have emerged from East Asian and South‐East Asian regions in recent years.

Ambient air concentrations of PCDD/Fs, coplanar PCBs, PBDD/Fs, and PBDEs and their impacts on vegetation and soil - Y.-C. Kuo; Y.-C. Chen; M.-Y. Lin; L.-H. Young; H.-T. Hsu; S.-H. Liou; T.-N. Wu; L.-C. Wang; P.-J. Tsai (International Journal of Environmental Science and Technology, 2015)

Infections of nervous necrosis virus in wild and cage‐reared marine fish from S outh C hina S ea with unexpected wide host ranges - X D Liu; J N Huang; S P Weng; X Q Hu; W J Chen; Z D Qin; X X Dong; X L Liu; Y Zhou; M Asim; W M Wang; J G He; et al. (Journal of Fish Diseases, 2015)
The concerns about the impact of the nervous necrosis virus ( NNV ) infections in wild fish have been raised. This paper presents the results of quarterly surveys of NNV in wild and cage‐reared marine fish from South China Sea. Samples of 892 wild fish belonging to 69 species and 381 cage‐reared fish belonging to 11 species were collected and were detected by seminested PCR and nested PCR . In the case of seminested PCR , the positive signal was detected in 3.0% and 3.1% samples of wild and cage‐reared fish, respectively. However, by nested RT ‐ PCR , the positive signal was observed in 42.3% and 63.0% samples of wild and cage‐reared fish, respectively. If the fish species were considered, the positive signal was detected in 21.7% and 72.7% species of wild and cage‐reared fish by seminested PCR assay, respectively. However, by nested RT ‐ PCR , the positive signal was observed in 65.2% and 100% species of wild and cage‐reared fish, respectively. The nucleotide sequences of the nested PCR products were determined. Phylogenetic tree showed that all the obtained viral isolates belonged to the red‐spotted grouper nervous necrosis virus ( RGNNV ) genotype. Thirty‐five species of the marine fish were the new hosts of NNV .

Mass mortality associated with a viral‐induced anaemia in cage‐reared large yellow croaker, Larimichthys crocea (Richardson) - W J Xu; Z D Qin; H Shi; N Jiang; Y Zhou; X L Liu; J J Xie; G S Wang; W M Wang; M Asim; L B Zeng; L Lin (Journal of Fish Diseases, 2015)

Clustering of Clinical and Environmental Escherichia coli O104 Isolates Using the DiversiLab™ Repetitive Sequence-Based PCR System - N. M. Herbold; L. M. Clotilde; K. M. Anderson; J. Kase; G. L. Hartman; S. Himathongkham; A. Lin; C. R. Lauzon (Current Microbiology, 2015)

Clinical manifestations and prognostic factors of Morganella morganii bacteremia - T.-Y. Lin; M.-C. Chan; Y.-S. Yang; Y. Lee; K.-M. Yeh; J.-C. Lin; F.-Y. Chang (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

ICE1 demethylation drives the range expansion of a plant invader through cold tolerance divergence - H. J. Xie; H. Li; D. Liu; W. M. Dai; J. Y. He; S. Lin; H. Duan; L. L. Liu; S. G. Chen; X. L. Song; B. E. Valverde; S. Qiang (Molecular Ecology, 2015)
Cold tolerance adaption is a crucial determinant for the establishment and expansion of invasive alien plants into new cold environments; however, its evolutionary mechanism is poorly understood. Crofton weed ( Ageratina adenophora ), a highly invasive alien plant, is continuously spreading across subtropical areas in China, north‐eastward from the first colonized south‐western tropical regions, through cold tolerance evolution. Close relations between the cold tolerance levels of 34 populations, represented by 147 accessions, and the latitude, extreme lowest temperature, coldest month average temperature, and invasion period have provided direct insight into its cold tolerance divergence. A comparative study of the CBF pathway, associated with the cold tolerance enhancement of cold‐susceptible CBF 1 ‐transgenic plant, among four geographically distinct crofton weed populations revealed that the CBF pathway plays a key role in the observed cold tolerance divergence. Four epialleles of the cold response regulator ICE 1 ranged from 66 to 50 methylated cytosines, representing a 4.4% to 3.3% methylation rate and significantly corresponding to the lowest to highest cold tolerance levels among these different populations. The significant negative relation between the transcription levels of the primary CBF pathway members, except for CBF 2 , and the methylation levels among the four populations firstly demonstrates that the demethylation‐upregulated transcription level of CBF pathway is responsible for this evolution. These facts, combined with the cold tolerance variation and methylation found among three native and two other introduced populations, indicate that the ICE 1‐ demethylated upregulation of cold tolerance may be the underlying evolutionary mechanism allowing crofton weed to expand northward in China.

AdeRS combination codes differentiate the response to efflux pump inhibitors in tigecycline-resistant isolates of extensively drug-resistant Acinetobacter baumannii - J.-R. Sun; C.-L. Perng; J.-C. Lin; Y.-S. Yang; M.-C. Chan; T.-Y. Chang; F.-M. Lin; T.-S. Chiueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

TM4SF1: a new vascular therapeutic target in cancer - Chi-Iou Lin; Anne Merley; Tracey E. Sciuto; Dan Li; Ann M. Dvorak; Juan M. Melero-Martin; Harold F. Dvorak; Shou-Ching S. Jaminet (Angiogenesis, 2014)

The association between chronic osteomyelitis and increased risk of diabetes mellitus: a population-based cohort study - S.-Y. Lin; C.-L. Lin; C.-H. Tseng; I.-K. Wang; S.-M. Wang; C.-C. Huang; Y.-J. Chang; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Erratum to: Increased risk of chronic fatigue syndrome following herpes zoster: a population-based study - S.-Y. Tsai; T.-Y. Yang; H.-J. Chen; C.-S. Chen; W.-M. Lin; W.-C. Shen; C.-N. Kuo; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Increased risk of pulmonary tuberculosis among patients with appendectomy in Taiwan - S.-W. Lai; C.-L. Lin; K.-F. Liao; S.-M. Tsai (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Increased risk of chronic fatigue syndrome following herpes zoster: a population-based study - S.-Y. Tsai; T.-Y. Yang; H.-J. Chen; C.-S. Chen; W.-M. Lin; W.-C. Shen; C.-N. Kuo; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Molecular characterization of a new member of the 16SrV group of phytoplasma associated with Bischofia polycarpa (Levl.) Airy Shaw witches’ -broom disease in China by a multiple gene-based analysis - F. Lai; C. S. Song; Z. G. Ren; C. L. Lin; Q. C. Xu; Y. Li; C. G. Piao; S. S. Yu; M. W. Guo; G. Z. Tian (Australasian Plant Pathology, 2014)

A Review of the Genus Pielomastax Chang (Orthoptera: Eumastacoidea) from China with Description of a New Species - L L Lin; Z M Zheng; R Yang; S Q Xu (Neotropical Entomology, 2014)

Sulfur sources of sedimentary “buckshot” pyrite in the Auriferous Conglomerates of the Mesoarchean Witwatersrand and Ventersdorp Supergroups, Kaapvaal Craton, South Africa - B. M. Guy; S. Ono; J. Gutzmer; Y. Lin; N. J. Beukes (Mineralium Deposita, 2014)

Nanomedicine for glaucoma: sustained release latanoprost offers a new therapeutic option with substantial benefits over eyedrops - Tina T. Wong; Gary D. Novack; Jayaganesh V. Natarajan; Ching Lin Ho; Hla M. Htoon; Subbu S. Venkatraman (Drug Delivery and Translational Research, 2014)

Development of a selective and differential medium for capsulated L actococcus garvieae - C‐I Chang; C‐F Lee; J‐M Tsai; C‐C Wu; L‐H Chen; S‐C Chen; K‐J Lin (Journal of Fish Diseases, 2014)
A selective and differential medium termed ‘ LG agar’ was developed for the isolation and presumptive identification of L actococcus garvieae that results in black colonies with red halos. In this study, all 14 strains of L . garvieae and only 9 of the 148 strains representing 38 other species were able to grow on the LG agar. The nine viable strains on LG agar plates (including E nterococcus faecalis , E nterococcus faecium , L actococcus lactis , V ibrio fluvialis , V ibrio furnissii , V ibrio mimicus and V ibrio salmonicida ) were further differentiated from L . garvieae by various colours or colony features. Colonies isolated from the mixing culture and the infected giant sea perch using LG agar plates were all positively identified as L . garvieae by conventional tests and 16 S r DNA sequencing. Furthermore, LG agar discriminated capsulated strains of L . garvieae , which were believed to be correlated with pathogens of fish and shellfish, from non‐capsulated ones by colony appearances. The specificity and differentiating ability of LG agar suggest that this medium displays considerable potential for primary isolation and presumptive identification of L . garvieae from pathological and environmental samples.

Eutrophication as a driver of r ‐selection traits in a freshwater fish - M. Lin; M. Chevalier; S. Lek; L. Zhang; R. E. Gozlan; J. Liu; T. Zhang; S. Ye; W. Li; Z. Li (Journal of Fish Biology, 2014)
This study tested whether eutrophication could influence life‐history traits of a cyprinid, Chanodichthys erythropterus , in 10 Chinese lakes. Using the von Bertalanffy growth model, the asymptotic length ( L ∞ ) and the growth performance index ( I GRO ) were significantly affected by eutrophication. The gonado‐somatic index ( I G ) and relative fecundity ( F R ) were significantly lower in mesotrophic lakes than in eutrophic and hypertrophic lakes. These results indicate that increasing eutrophication affects the life‐history tactics of a freshwater fish.

Peptides Regulate Expression of Signaling Molecules in Kidney Cell Cultures during In Vitro Aging - V. Kh. Khavinson; N. S. Lin’kova; V. O. Polyakova; A. O. Durnova; T. E. Nichik; I. M. Kvetnoi (Bulletin of Experimental Biology and Medicine, 2014)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

Trends in the susceptibility of methicillin-resistant Staphylococcus aureus to nine antimicrobial agents, including ceftobiprole, nemonoxacin, and tyrothricin: results from the Tigecycline In Vitro Surveillance in Taiwan (TIST) study, 2006–2010 - Y.-H. Chen; C.-Y. Liu; W.-C. Ko; C.-H. Liao; P.-L. Lu; C.-H. Huang; C.-T. Lu; Y.-C. Chuang; S.-M. Tsao; Y.-S. Chen; Y.-C. Liu; W.-Y. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Recommendations for the processing and storage of water samples before polymerase chain reaction (PCR) analysis - BJ Gilpin; M Devane; F Nourozi; B Robson; P Scholes; S Lin (New Zealand Journal of Marine and Freshwater Research, 2013)
A range of options for the storage and partial processing of water samples before polymerase chain reaction (PCR) analysis were evaluated. In addition, temporal storage of extracted DNA at 4 °C was investigated. Filtering the water sample and then storing that filter at −20 °C for up to six months before DNA extraction was equivalent to extracting DNA immediately. Freezing a water sample resulted in an immediate 1 log loss of PCR signal, although thereafter the sample was stable for at least three months. A rapid loss of detectable PCR product was found when storing a water sample at 4 °C for longer than one week. Extracted DNA could be stored at 4 °C for at least six months without considerable loss of PCR signal.

White spot syndrome virus epizootic in cultured P acific white shrimp L itopenaeus vannamei (Boone) in T aiwan - L Cheng; W‐H Lin; P‐C Wang; M‐A Tsai; J‐P Hsu; S‐C Chen (Journal of Fish Diseases, 2013)
White spot syndrome virus ( WSSV ) has caused significant losses in shrimp farms worldwide. Between 2004 and 2006, Pacific white shrimp L itopenaeus vannamei (Boone) were collected from 220 farms in T aiwan to determine the prevalence and impact of WSSV infection on the shrimp farm industry. Polymerase chain reaction ( PCR ) analysis detected WSSV in shrimp from 26% of farms. Juvenile shrimp farms had the highest infection levels (38%; 19/50 farms) and brooder shrimp farms had the lowest (5%; one of 20 farms). The average extent of infection at each farm was as follows for WSSV ‐positive farms: post‐larvae farms, 71%; juvenile farms, 61%; subadult farms, 62%; adult farms, 49%; and brooder farms, 40%. Characteristic white spots, hypertrophied nuclei and basophilic viral inclusion bodies were found in the epithelia of gills and tail fans, appendages, cephalothorax and hepatopancreas, and virions of WSSV were observed. Of shrimp that had WSSV lesions, 100% had lesions on the cephalothorax, 96% in gills and tail fans, 91% on appendages and 17% in the hepatopancreas. WSSV was also detected in copepoda and crustaceans from the shrimp farms. Sequence comparison using the pms146 gene fragment of WSSV showed that isolates from the farms had 99.7–100% nucleotide sequence identity with four strains in the G en B ank database – China ( AF332093 ), T aiwan ( AF440570 and U50923 ) and Thailand ( AF369029 ). This is the first broad study of WSSV infection in L . vannamei in T aiwan.

Photosynthesis of temperate E ucalyptus globulus trees outside their native range has limited adjustment to elevated CO 2 and climate warming - Kristine Y. Crous; Audrey G. Quentin; Yan‐Shih Lin; Belinda E. Medlyn; David G. Williams; Craig V. M. Barton; David S. Ellsworth (Global Change Biology, 2013)
E ucalyptus species are grown widely outside of their native ranges in plantations on all vegetated continents of the world. We predicted that such a plantation species would show high potential for acclimation of photosynthetic traits across a wide range of growth conditions, including elevated [ CO 2 ] and climate warming. To test this prediction, we planted temperate E ucalyptus globulus Labill. seedlings in climate‐controlled chambers in the field located >700 km closer to the equator than the nearest natural occurrence of this species. Trees were grown in a complete factorial combination of elevated CO 2 concentration ( eC ; ambient [ CO 2 ] +240 ppm) and air warming treatments ( eT ; ambient +3 °C) for 15 months until they reached ca. 10 m height. There was little acclimation of photosynthetic capacity to eC and hence the CO 2 ‐induced photosynthetic enhancement was large (ca. 50%) in this treatment during summer. The warming treatment significantly increased rates of both carboxylation capacity ( V cmax ) and electron transport ( J max ) (measured at a common temperature of 25 °C) during winter, but decreased them significantly by 20–30% in summer. The photosynthetic CO 2 compensation point in the absence of dark respiration ( Γ *) was relatively less sensitive to temperature in this temperate eucalypt species than for warm‐season tobacco. The temperature optima for photosynthesis and J max significantly changed by about 6 °C between winter and summer, but without further adjustment from early to late summer. These results suggest that there is an upper limit for the photosynthetic capacity of E . globulus ssp. globulus outside its native range to acclimate to growth temperatures above 25 °C. Limitations to temperature acclimation of photosynthesis in summer may be one factor that defines climate zones where E . globulus plantation productivity can be sustained under anticipated global environmental change.

Isolation and molecular analysis of genes Stpk-V2 and Stpk-V3 homologous to powdery mildew resistance gene Stpk-V in a Dasypyrum villosum accession and its derivatives - Z. S. Lin; Y. L. Zhang; M. J. Wang; J. R. Li; K. Wang; X. Chen; Q. F. Xu; X. S. Zhang; X. G. Ye (Journal of Applied Genetics, 2013)

The California Breast Cancer Survivorship Consortium (CBCSC): prognostic factors associated with racial/ethnic differences in breast cancer survival - Anna H. Wu; Scarlett Lin Gomez; Cheryl Vigen; Marilyn L. Kwan; Theresa H. M. Keegan; Yani Lu; Salma Shariff-Marco; Kristine R. Monroe; Allison W. Kurian; Iona Cheng; Bette J. Caan; Valerie S. Lee; et al. (Cancer Causes & Control, 2013)

Human white adipose tissue vasculature contains endothelial colony-forming cells with robust in vivo vasculogenic potential - Ruei-Zeng Lin; Rafael Moreno-Luna; Rocio Muñoz-Hernandez; Dan Li; Shou-Ching S. Jaminet; Arin K. Greene; Juan M. Melero-Martin (Angiogenesis, 2013)

Soluble interleukin‐1 receptor, a potential negative regulator of orange‐spotted grouper Epinephelus coioides interleukin‐1 system - D. Q. Lu; M. Yao; S. B. Yi; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2013)
In this study, the cDNA sequence encoding interleukin‐1 ( Il ‐1) receptor‐like protein of orange‐spotted grouper Epinephelus coioides was obtained. The newly identified sequence was named soluble type I Il ‐1 receptor ( sIl‐1rI ) owing to its structural composition, which had two Ig‐like domains, lack of transmembrane region and the Toll/interleukin‐1 receptor ( TIR ) domain, similar to the brown rat Rattus norvegicus soluble Il‐1rI . In addition, sequence comparison and phylogenetic analysis indicated that E. coioides sequence had a closer relationship with Il‐1rI than Il‐1rII . Real‐time PCR revealed that sil‐1rI mRNA expression presented a process of decrease, restoration and increase in Cryptocaryon irritans ‐infected E. coioides . The negative correlation between Il ‐1β and sil‐1rI mRNA in C. irritans ‐infected head‐kidney implied the potential negative regulatory role of sil‐1rI in E. coioides Il ‐1 system. The leucocytes incubated with lipopolysaccharide or polyriboinosinic polyribocytidylic acid exhibited different expression profiles of sil‐1rI . Recombinant Il ‐1β ( rIl ‐1β) protein was capable of inducing sil‐1rI mRNA under the concentration of 100 ng ml −1 , suggesting that high dosage or excess Il ‐1β would stimulate the expression of sil‐1rI to maintain the homoeostasis of E. coioides Il ‐1 system. For the first time, the role of teleost Il‐1rI in parasite infection has been identified, and soluble Il‐1r was found in fish.

The use of procalcitonin in the diagnosis of bone and joint infection: a systemic review and meta-analysis - C.-J. Shen; M.-S. Wu; K.-H. Lin; W.-L. Lin; H.-C. Chen; J.-Y. Wu; M. C.-H. Lee; C.-C. Lee (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Outcome of metastatic breast cancer in selected women with or without deleterious BRCA mutations - S. Bayraktar; A. M. Gutierrez-Barrera; H. Lin; N. Elsayegh; T. Tasbas; J. K. Litton; N. K. Ibrahim; P. K. Morrow; M. Green; V. Valero; D. J. Booser; G. N. Hortobagyi; et al. (Clinical & Experimental Metastasis, 2013)

Characterization of a novel cell line from the caudal fin of koi carp Cyprinus carpio - S.‐L. Lin; Y.‐H. Cheng; C.‐M. Wen; S.‐N. Chen (Journal of Fish Biology, 2013)
A continuous cell line ( KF ‐101) derived from the caudal fin of the koi carp Cyprinus carpio was established and characterized. The KF ‐101 cell line multiplied abundantly in Leibovitz's L‐15 medium containing 10% foetal bovine serum at 25° C, and was subcultured for >90 passages over a period of 3 years. Immunocytochemistry revealed that the KF ‐101 cells contain keratin, junction proteins connexin‐43 and occludin, and ectodermal stem‐cell marker Pax‐6, but not vimentin. Furthermore, the KF ‐101 cells reacted with anti‐human DARPP ‐32 and anti‐human GATA ‐4 antibodies, and the labelling was regulated according to the cell cycle. The labels of the DARPP ‐32 and GATA ‐4 antibodies in the KF ‐101 cells were the suggested phosphatase‐1 inhibitor‐1 and GATA ‐3, respectively. In addition, the KF ‐101 cells were susceptible to koi herpesvirus but were resistant to eel herpesvirus, iridovirus, grouper nodavirus and chum salmon ( Oncorhynchus keta ) virus. The results indicate that the KF ‐101 cells are suitable materials for investigating biological and virological development.

Sex identification in the Collared Scops Owl (Otus bakkamoena) with novel markers generated by random amplified polymorphic DNA - P. H. Wang; H. A. Hsu; M. C. Chao; F. T. Chan; L. M. Wang; P. I. Lin; H. S. Tsao; H. W. Yuan; C. C. Chen; S. T. Ding (Conservation Genetics Resources, 2013)

HOXB13 is a susceptibility gene for prostate cancer: results from the International Consortium for Prostate Cancer Genetics (ICPCG) - Jianfeng Xu; Ethan M. Lange; Lingyi Lu; Siqun L. Zheng; Zhong Wang; Stephen N. Thibodeau; Lisa A. Cannon-Albright; Craig C. Teerlink; Nicola J. Camp; Anna M. Johnson; Kimberly A. Zuhlke; Janet L. Stanford; et al. (Human Genetics, 2013)

Development of microsatellite markers in an ungulate mammal, the Formosan serow (Capricornis swinhoei) - Y. Y. Chang; M. C. Chao; S. T. Ding; E.-C. Lin; H. S. Tsao; H. W. Yuan; P. H. Wang (Conservation Genetics Resources, 2012)

Large-scale collection and annotation of gene models for date palm (Phoenix dactylifera, L.) - Guangyu Zhang; Linlin Pan; Yuxin Yin; Wanfei Liu; Dawei Huang; Tongwu Zhang; Lei Wang; Chengqi Xin; Qiang Lin; Gaoyuan Sun; Mohammed M. Ba Abdullah; Xiaowei Zhang; et al. (Plant Molecular Biology, 2012)

Chronic aspiration shifts the immune response from adaptive immunity to innate immunity in a murine model of asthma - Kuei-Ying Su; Anitra D. Thomas; Jui-Chih Chang; Jason H. Leung; Sean M. Lee; Zoie E. Holzknecht; Mary Lou Everett; W. Michael Foster; Monica Kraft; William Parker; R. Duane Davis; Shu S. Lin (Inflammation Research, 2012)

Tetrapeptide H-Ala-Glu-Asp-Arg-OH Stimulates Expression of Cytoskeletal and Nuclear Matrix Proteins - V. Kh. Khavinson; N. S. Lin’kova; V. O. Polyakova; I. M. Kvetnoy; V. V. Benberin; M. M. D’yakonov; Yu. S. Titkov (Bulletin of Experimental Biology and Medicine, 2012)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Regional variation in otolith Sr:Ca ratios of African longfinned eel Anguilla mossambica and mottled eel Anguilla marmorata : a challenge to the classic tool for reconstructing migratory histories of fishes - Y.‐J. Lin; B. M. Jessop; O. L. F. Weyl; Y. Iizuka; S.‐H. Lin; W.‐N. Tzeng; C.‐L. Sun (Journal of Fish Biology, 2012)
Otolith Sr:Ca ratios of the African longfinned eel Anguilla mossambica and giant mottled eel Anguilla marmorata from nine freshwater sites in four rivers of South Africa were analysed to reconstruct their migratory life histories between freshwater and saltwater habitats. For A. mossambica , the Sr:Ca ratios in the otolith edge differed significantly among rivers and had large effect sizes, but did not differ among sites within a river. Otolith Sr:Ca ratios did not differ among rivers for A. marmorata . When rivers were pooled, the edge Sr:Ca ratios of A. mossambica were not significantly different from those of A. marmorata . According to the river‐specific critical Sr:Ca ratio distinguishing freshwater from saltwater residence, most A. mossambica and A. marmorata had saltwater habitat experience after settlement in fresh water. This was primarily during their elver stage or early in the yellow eel stage. During the middle and late yellow eel stage, freshwater residency was preferred and only sporadic visits were made to saltwater habitats. The data also suggest that regional variations in otolith Sr:Ca ratios affect the critical Sr:Ca value and are a challenge for the reconstruction of migratory life histories that should be explicitly considered to avoid bias and uncertainty.

Identification and expression analysis of major histocompatibility complex IIB gene in orange‐spotted grouper Epinephelus coioides - D. Q. Lu; S. B. Yi; M. Yao; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2012)
In this study, complementary DNA (cDNA) and DNA sequences of major histocompatibility complex (MHC) class IIB genes ( mhcIIB ) were cloned from orange‐spotted grouper Epinephelus coioides . The gene structure of E. coioides mhcIIB consists of five exons and four introns, and its deduced amino acid sequence length is 249 amino acids, including a signal peptide, a peptide‐binding region, an IGC1 domain, a transmembrane region and a cytoplasmic tail. A phylogenetic study showed that E. coioides mhcIIB shared 32·0–79·1% identity with those of other teleosts and mammals. Real‐time reverse transcriptase (RT)‐PCR was performed to detect the class IIB gene expression in eight different tissues. To characterize the relationship between E. coioides mhcIIB gene and pathogens, in vivo and in vitro studies were performed. Challenge of Cryptocaryon irritans revealed that class IIB genes were down‐regulated after 24 and 48 h of challenge, and their expression was later restored at 72 h. Stimulation of isolated E. coioides leukocytes with lipopolysaccharide (LPS) and polyinosinic:polycytidylic acid (PolyI:C) significantly increased peripheral blood and spleen mhcIIB expression, while head kidney mhcIIB expression remained constant.

Enhancing a Cancer Prevention and Control Curriculum Through Interactive Group Discussions - L. P. Forsythe; S. M. Gadalla; J. G. Hamilton; B. M. Heckman-Stoddard; E. E. Kent; G. Y. Lai; S. W. Lin; P. Luhn; J. M. Faupel-Badger (Journal of Cancer Education, 2012)

Reemerging of enterovirus 71 in Taiwan: the age impact on disease severity - S.-M. Wang; T.-S. Ho; H.-C. Lin; H.-Y. Lei; J.-R. Wang; C.-C. Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

A review of magnetic resonance imaging and diffusion tensor imaging findings in mild traumatic brain injury - M. E. Shenton; H. M. Hamoda; J. S. Schneiderman; S. Bouix; O. Pasternak; Y. Rathi; M.-A. Vu; M. P. Purohit; K. Helmer; I. Koerte; A. P. Lin; C.-F. Westin; et al. (Brain Imaging and Behavior, 2012)

Peptidergic Regulation of Expression of Genes Encoding Antioxidant and Anti-Inflammatory Proteins - V. Kh. Khavinson; N. S. Lin’kova; A. V. Dudkov; V. O. Polyakova; I. M. Kvetnoi (Bulletin of Experimental Biology and Medicine, 2012)

Differential expression profiling of orange‐spotted grouper larvae, Epinephelus coioides (Hamilton), that survived a betanodavirus outbreak - M‐S Wu; C‐W Chen; C‐H Lin; C‐S Tzeng; C‐Y Chang (Journal of Fish Diseases, 2012)
Nervous necrosis virus (NNV), a piscine nodavirus, has caused serious viral nervous necrosis and viral encephalopathy and retinopathy in hatchery‐reared larvae and juveniles of a wide range of marine teleost species worldwide in the last two decades. Although the mortality of NNV‐infected larvae is nearly 100%, there are still some larvae that survive this catastrophe. To comprehensively understand the variations of these survivors at the molecular level, we collected orange‐spotted grouper larvae that survived an NNV outbreak in an indoor hatchery in southern Taiwan to study differential gene expression. Healthy larvae with high, medium and low levels of detected NNV were compared with morbid larvae using a 9600‐clone‐containing grouper larva cDNA microarray, and differential gene expression was further confirmed by a quantitative real‐time polymerase chain reaction. Significant variation exists in healthy larvae. The following genes were upregulated: adenylate kinase 1‐2, myosin binding protein H‐like, myosin light chain 2, myosin light chain 3, tropomyosin, fast/white muscle troponin T embryonic isoform, and parvalbumin 1 and 2 genes. The following genes were downregulated: apolipoprotein A‐I, trypsinogen, pyruvate kinase and astacin‐like metalloprotease. Moreover, immunoglobulin M heavy chain gene transcription was significantly higher in healthy larvae that had high virus levels, indicating that humoral immunity might protect organisms from viral infection. These results suggest that some non‐immune‐related genes may have played important roles in survival during the larval metamorphosis stage, after betanodavirus infection.

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Biodegradation of Cypermethrin by a newly isolated actinomycetes HU-S-01 from wastewater sludge - Q. S. Lin; S. H. Chen; M. Y. Hu; M. R. Ul Haq; L. Yang; H. Li (International Journal of Environmental Science and Technology, 2011)

Bacteremia caused by Brevundimonas species at a tertiary care hospital in Taiwan, 2000–2010 - M. R. Lee; Y. T. Huang; C. H. Liao; T. Y. Chuang; C. K. Lin; S. W. Lee; C. C. Lai; C. J. Yu; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

A multivalent vaccine for type 1 diabetes skews T cell subsets to Th2 phenotype in NOD mice - Ming S. Lin; Hubert M. Tse; Meghan M. Delmastro; Suzanne Bertera; Caterina T. Wong; Robert Lakomy; Jing He; Martha M. Sklavos; Gina M. Coudriet; Massimo Pietropaolo; Massimo M. Trucco; Jon D. Piganelli (Immunologic Research, 2011)

Peptidergic Regulation of Thymocyte Differentiation, Proliferation, and Apoptosis during Aging of the Thymus - N. S. Lin’kova; V. O. Polyakova; A. V. Trofimov; I. M. Kvetnoy; V. Kh. Khavinson (Bulletin of Experimental Biology and Medicine, 2011)

The controlled in vitro susceptibility of gastrointestinal pathogens to the antibacterial effect of manuka honey - S. M. Lin; P. C. Molan; R. T. Cursons (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Quantitative trait loci for temperature-sensitive resistance to Puccinia striiformis f. sp. tritici in wheat cultivar Flinor - J. Feng; L. L. Zuo; Z. Y. Zhang; R. M. Lin; Y. Y. Cao; S. C. Xu (Euphytica, 2011)

QTL analysis and candidate gene mapping for skin and flesh color in sweet cherry fruit (Prunus avium L.) - Suneth S. Sooriyapathirana; Amjad Khan; Audrey M. Sebolt; Dechun Wang; Jill M. Bushakra; Kui Lin-Wang; Andrew C. Allan; Susan E. Gardiner; David Chagné; Amy F. Iezzoni (Tree Genetics & Genomes, 2010)

Groundwater Assessment at Manukan Island, Sabah: Multidisplinary Approaches - S. M. Praveena; C. Y. Lin; A. Z. Aris; M. H. Abdullah (Natural Resources Research, 2010)

Genetic polymorphisms of the DNA repair geneMPG may be associated with susceptibility to rheumatoid arthritis - S. Y. Chen; L. Wan; C. M. Huang; Y. C. Huang; J. J. C. Sheu; Y. J. Lin; S. P. Liu; Y. C. Lan; C. H. Lai; C. W. Lin; C. H. Tsai; F. J. Tsai (Journal of Applied Genetics, 2010)

Development of EST-PCR markers for Thinopyrum intermedium chromosome 2Ai#2 and their application in characterization of novel wheat-grass recombinants - M. J. Wang; Y. Zhang; Z. S. Lin; X. G. Ye; Y. P. Yuan; W. Ma; Z. Y. Xin (Theoretical and Applied Genetics, 2010)

Cultivation‐independent characterization of ‘ Candidatus Magnetobacterium bavaricum’ via ultrastructural, geochemical, ecological and metagenomic methods - C. Jogler; M. Niebler; W. Lin; M. Kube; G. Wanner; S. Kolinko; P. Stief; A. J. Beck; D. de Beer; N. Petersen; Y. Pan; R. Amann; et al. (Environmental Microbiology, 2010)
Summary ‘ Candidatus Magnetobacterium bavaricum’ is unusual among magnetotactic bacteria (MTB) in terms of cell size (8–10 µm long, 1.5–2 µm in diameter), cell architecture, magnetotactic behaviour and its distinct phylogenetic position in the deep‐branching Nitrospira phylum. In the present study, improved magnetic enrichment techniques permitted high‐resolution scanning electron microscopy and energy dispersive X‐ray analysis, which revealed the intracellular organization of the magnetosome chains. Sulfur globule accumulation in the cytoplasm point towards a sulfur‐oxidizing metabolism of ‘ Candidatus M. bavaricum’. Detailed analysis of ‘ Candidatus M. bavaricum’ microhabitats revealed more complex distribution patterns than previously reported, with cells predominantly found in low oxygen concentration. No correlation to other geochemical parameters could be observed. In addition, the analysis of a metagenomic fosmid library revealed a 34 kb genomic fragment, which contains 33 genes, among them the complete rRNA gene operon of ‘ Candidatus M. bavaricum’ as well as a gene encoding a putative type IV RubisCO large subunit.

The chondroprotective effects of ferulic acid on hydrogen peroxide-stimulated chondrocytes: inhibition of hydrogen peroxide-induced pro-inflammatory cytokines and metalloproteinase gene expression at the mRNA level - M. P. Chen; S. H. Yang; C. H. Chou; K. C. Yang; C. C. Wu; Y. H. Cheng; Feng-Huei Lin (Inflammation Research, 2010)

Dopaminergic neurotoxicity following pulmonary exposure to manganese-containing welding fumes - Krishnan Sriram; Gary X. Lin; Amy M. Jefferson; Jenny R. Roberts; Rebecca S. Chapman; Bean T. Chen; Joleen M. Soukup; Andrew J. Ghio; James M. Antonini (Archives of Toxicology, 2010)

Antibacterial effect of electrolysed acid water on the nasal discharge from patients with chronic rhinosinusitis - R.-S. Jiang; S.-H. Wu; K.-L. Liang; J.-F. Lin; M.-C. Su; W.-K. Chen; F.-J. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

In vitro activities of doripenem and other carbapenems against clinically important bacteria isolated in intensive care units: nationwide data from the SMART Programme - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Establishment, characterization, virus susceptibility and transfection of cell lines from cobia, Rachycentron canadum (L.), brain and fin - T‐C Cheng; Y‐S Lai; I‐Y Lin; C‐P Wu; S‐L Chang; T‐I Chen; M‐S Su (Journal of Fish Diseases, 2010)
Establishment and characterization of two cobia, Rachycentron canadum, cell lines derived from cobia brain (CB) and cobia fin (CF) are described. Caudal fin and brain from juvenile cobia were dissociated for 30 and 10 min, respectively, in phosphate‐buffered saline containing 0.25% trypsin at 25 °C. The optimal culture condition for both dissociated cells (primary cell culture) was at 28 °C in Leibovitz‐15 medium containing 10% foetal bovine serum. The cells have been sub‐cultured at a ratio of 1:2 for more than 160 passages over a period of 3 years. Origin of the cultured cells was verified by comparison of their sequences of mitochondrial cytochrome oxidase subunit I genes ( cox I ) with the cox 1 sequence from cobia muscle tissue. The cell lines showed polyploidy. No mycoplasma contamination was detected. Susceptibility to grouper iridovirus was observed for the CB cell line but not the CF cell line. Both cell lines expressed green fluorescent protein after being transfected with green fluorescent reporter gene driven by the cytomegalovirus promoter.

The importance of myocardial amino acids during ischemia and reperfusion in dilated left ventricle of patients with degenerative mitral valve disease - A. Venturini; R. Ascione; H. Lin; E. Polesel; G. D. Angelini; M.-S. Suleiman (Molecular and Cellular Biochemistry, 2009)

Intercomparison, interpretation, and assessment of spring phenology in North America estimated from remote sensing for 1982–2006 - MICHAEL A. WHITE; KIRSTEN M. De BEURS; KAMEL DIDAN; DAVID W. INOUYE; ANDREW D. RICHARDSON; OLAF P. JENSEN; JOHN O'KEEFE; GONG ZHANG; RAMAKRISHNA R. NEMANI; WILLEM J. D. Van LEEUWEN; JESSLYN F. BROWN; ALLARD De WIT; et al. (Global Change Biology, 2009)
Shifts in the timing of spring phenology are a central feature of global change research. Long‐term observations of plant phenology have been used to track vegetation responses to climate variability but are often limited to particular species and locations and may not represent synoptic patterns. Satellite remote sensing is instead used for continental to global monitoring. Although numerous methods exist to extract phenological timing, in particular start‐of‐spring (SOS), from time series of reflectance data, a comprehensive intercomparison and interpretation of SOS methods has not been conducted. Here, we assess 10 SOS methods for North America between 1982 and 2006. The techniques include consistent inputs from the 8 km Global Inventory Modeling and Mapping Studies Advanced Very High Resolution Radiometer NDVIg dataset, independent data for snow cover, soil thaw, lake ice dynamics, spring streamflow timing, over 16 000 individual measurements of ground‐based phenology, and two temperature‐driven models of spring phenology. Compared with an ensemble of the 10 SOS methods, we found that individual methods differed in average day‐of‐year estimates by ±60 days and in standard deviation by ±20 days. The ability of the satellite methods to retrieve SOS estimates was highest in northern latitudes and lowest in arid, tropical, and Mediterranean ecoregions. The ordinal rank of SOS methods varied geographically, as did the relationships between SOS estimates and the cryospheric/hydrologic metrics. Compared with ground observations, SOS estimates were more related to the first leaf and first flowers expanding phenological stages. We found no evidence for time trends in spring arrival from ground‐ or model‐based data; using an ensemble estimate from two methods that were more closely related to ground observations than other methods, SOS trends could be detected for only 12% of North America and were divided between trends towards both earlier and later spring.

Nationwide surveillance of antimicrobial resistance among Haemophilus influenzae and Streptococcus pneumoniae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Prevalence of helminths in water buffaloes in Hunan Province, China - Y. Liu; F. Li; W. Liu; R. S. Dai; Y. M. Tan; D. S. He; R. Q. Lin; X. Q. Zhu (Tropical Animal Health and Production, 2009)

The in vitro susceptibility of Campylobacter spp. to the antibacterial effect of manuka honey - S. M. Lin; P. C. Molan; R. T. Cursons (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

A quick and efficient approach for gene silencing by using triple putative microRNA-based short hairpin RNAs - Z. X. Shan; Q. X. Lin; M. Yang; C. Y. Deng; S. J. Kuang; Z. L. Zhou; D. Z. Xiao; X. Y. Liu; S. G. Lin; X. Y. Yu (Molecular and Cellular Biochemistry, 2009)

Nationwide surveillance of antimicrobial resistance among Enterobacteriaceae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Group A streptococcal infection caused by emm1 strains among children in southern Taiwan - H.-C. Lin; S.-M. Wang; Y.-L. Lin; Y.-S. Lin; J.-J. Wu; W.-J. Chuang; M. T. Lin; C.-C. Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Induction potential of clavulanic acid toward L1 and L2 β-lactamases of Stenotrophomonas maltophilia - C.-W. Lin; R.-M. Hu; S.-C. Huang; Y.-J. Hsiao; T.-C. Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Relationships between physiological responses and presyncope symptoms during tilting up in patients with spinal cord injury - David S. Liu; Walter H. Chang; Alice M. K. Wong; Shih-Ching Chen; Kang-Ping Lin; Chien-Hung Lai (Medical & Biological Engineering & Computing, 2008)

Residential proximity to large airports and potential health impacts in New York State - S. Lin; J. P. Munsie; M. Herdt-Losavio; S. A. Hwang; K. Civerolo; K. McGarry; T. Gentile (International Archives of Occupational and Environmental Health, 2008)

Ethmoid sinus mycology of chronic rhinosinusitis - R. S. Jiang; K. L. Liang; J. Y. Shiao; J. F. Lin; M. C. Su; C. H. Hsin; F. J. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Determination of Particulate-Bound Formaldehyde from Burning Incense by Solid Phase Microextraction - S. W. Liou; C. Y. Chen; T. T. Yang; J. M. Lin (Bulletin of Environmental Contamination and Toxicology, 2008)

Detection of quantitative trait loci controlling extremely early heading in rice - Y. Nonoue; K. Fujino; Y. Hirayama; U. Yamanouchi; S. Y. Lin; M. Yano (Theoretical and Applied Genetics, 2008)

Using FANP approach on selection of competitive priorities based on cleaner production implementation: a case study in PCB manufacturer, Taiwan - M. L. Tseng; Y. H. Lin; A. S. F. Chiu; J. C. H. Liao (Clean Technologies and Environmental Policy, 2008)

Development of a biofeedback tilt-table for investigating orthostatic syncope in patients with spinal cord injury - David S. Liu; Walter H. Chang; Alice M. K. Wong; Shih-Ching Chen; Kang-Ping Lin; Chien-Hung Lai (Medical & Biological Engineering & Computing, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Characteristics of Emissions of Volatile Organic Compounds from Smoldering Incense - T. T. Yang; T. S. Lin; M. Chang (Bulletin of Environmental Contamination and Toxicology, 2007)

Health behaviors of cancer survivors: data from an Australian population-based survey - Elizabeth G. Eakin; Danny R. Youlden; Peter D. Baade; Sheleigh P. Lawler; Marina M. Reeves; Jane S. Heyworth; Lin Fritschi (Cancer Causes & Control, 2007)

Image processing of FORMOSAT‐2 data for monitoring the South Asia tsunami - C.‐C. Liu; J.‐G. Liu; C.‐W. Lin; A.‐M. Wu; S.‐H. Liu; C.‐L. Shieh (International Journal of Remote Sensing, 2007)

Ganoderma lucidum polysaccharide peptide reduced the production of proinflammatory cytokines in activated rheumatoid synovial fibroblast - Y. W. Ho; J. S. L. Yeung; P. K. Y. Chiu; W. M. Tang; Z. B. Lin; R. Y. K. Man; C. S. Lau (Molecular and Cellular Biochemistry, 2007)

Endosperm-specific hypomethylation, and meiotic inheritance and variation of DNA methylation level and pattern in sorghum (Sorghum bicolor L.) inter-strain hybrids - M. S. Zhang; H. Y. Yan; N. Zhao; X. Y. Lin; J. S. Pang; K. Z. Xu; L. X. Liu; B. Liu (Theoretical and Applied Genetics, 2007)

Arsenic Distribution in a Tilapia (Oreochromis mossambicus) Water-Sediment Aquacultural Ecosystem in Blackfoot Disease Hyperendemic Areas - S. -W. Wang; K. -H. Lin; Y. -M. Hsueh; C. -W. Liu (Bulletin of Environmental Contamination and Toxicology, 2007)

Accumulation of additive effects generates a strong photoperiod sensitivity in the extremely late-heading rice cultivar ‘Nona Bokra’ - Y. Uga; Y. Nonoue; Z. W. Liang; H. X. Lin; S. Yamamoto; U. Yamanouchi; M. Yano (Theoretical and Applied Genetics, 2007)

A numerical study of the influence of urban expansion on monthly climate in dry autumn over the Pearl River Delta, China - W. S. Lin; C.-H. Sui; L. M. Yang; X. M. Wang; R. R. Deng; S. J. Fan; C. S. Wu; A. Y. Wang; S. K. Fong; H. Lin (Theoretical and Applied Climatology, 2007)

Apoptosis-dependent and -independent mechanisms mediate the phagocytic recognition/clearance of the HL60-A1 transfectants with prolonged survival - C.-L. Chou; L.-L. Chiang; C.-T. Yu; H.-C. Chen; K.-Y. Lee; S.-M. Lin; C.-D. Huang; W.-T. Liu; P.-C. Chou; C.-H. Wang; H.-C. Lin; H.-P. Kuo; et al. (Inflammation Research, 2007)

A dual site study of the rainwater chemistry within the Western Pacific region - K. M. Wai; S. H. Wang; P. A. Tanner; N. H. Lin (Journal of Atmospheric Chemistry, 2007)

The contents and forms of solid-phase species of radioactive strontium and cesium in Taiwan soils - S. W. Chang Chien; M. C. Wang; C. L. Chiu; Yu-Ming Lin; Shu-Ying Lai (Environmental Monitoring and Assessment, 2007)

Isolation of Endophytic Actinomycetes from Different Cultivars of Tomato and their Activities Against Ralstonia solanacearum in Vitro - H. M. Tan; L. X. Cao; Z. F. He; G. J. Su; B. Lin; S. N. Zhou (World Journal of Microbiology and Biotechnology, 2006)

Characterizing the severe turbulence environments associated with commercial aviation accidents. A real-time turbulence model (RTTM) designed for the operational prediction of hazardous aviation turbulence environments - M. L. Kaplan; J. J. Charney; K. T. Waight; K. M. Lux; J. D. Cetola; A. W. Huffman; A. J. Riordan; S. D. Slusser; M. T. Kiefer; P. S. Suffern; Y.-L. Lin (Meteorology and Atmospheric Physics, 2006)

Serum Heat Shock Protein (HSP70) and Its Antibody (Anti-HSP70) Levels in Male Foundry Workers in Taiwan - C.-J. Chen; H.-J. Wen; S.-H. Liu; M.-S. Lin; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2006)

Computational Simulations of the Human Magneto- and Electroenterogram - A. S. Lin; M. L. Buist; L. K. Cheng; N. P. Smith; A. J. Pullan (Annals of Biomedical Engineering, 2006)

Albino inflorescence proliferation of Dendrocalamus latiflorus - C. S. Lin; M. C. Tseng; P. I. Hong; W. C. Chang (In Vitro Cellular & Developmental Biology - Plant, 2006)

Enhancement of chemosensitivity toward peplomycin by calpastatin-stabilized NF-κB p65 in esophageal carcinoma cells: possible involvement of Fas/Fas-L synergism - T.-L. Liu; H. Shimada; T. Ochiai; T. Shiratori; S.-E. Lin; M. Kitagawa; K. Harigaya; M. Maki; M. Oka; T. Abe; M. Takiguchi; T. Hiwasa (Apoptosis, 2006)

Enhanced viability of a nervous necrosis virus‐infected stable cell line over‐expressing a fusion product of the zfBcl‐x L and green fluorescent protein genes - S‐P Chen; H‐L Yang; H‐Y Lin; M‐C Chen; J‐L Wu; J‐R Hong (Journal of Fish Diseases, 2006)
Nervous necrosis virus (NNV) infection induces host cell apoptosis by an ill‐understood process. We utilized a fusion between enhanced green fluorescent protein (EGFP) and the zfBcl‐x L gene in GL‐av cells to select for zfBcl‐x L stable cell lines and to assess the effectiveness of the anti‐apoptotic protein Bcl‐x L in circumventing NNV‐induced cell death. Stable EGFP and EGFP‐Bcl‐x L ‐expressing clones were obtained at high purity within 2.5–3 months. In the latter, the EGFP‐Bcl‐x L fusion protein (approximately 58.2 kDa, as ascertained by Western blot) was predominantly targeted to mitochondria. We assayed for apoptosis in red‐spotted grouper NNV Tainan no. 1 (RGNNV TN1)‐infected cells with terminal deoxynucleotidyl transferase (TdT)‐mediated end labelling (TUNEL) of DNA at different virus doses. NNV infection of NNV Bcl‐x L GL‐av cell line revealed a protective effect, with a decrease in TUNEL‐positive cells of 7%, 8% and 31.8% at 24, 48 and 72 h, respectively. In addition, RGNNV infection of the Bcl‐x L GL‐av cell line revealed a protective effect, with an enhanced viability of 3%, 40% and 73% at 24, 48, and 72 h, respectively. We conclude that NNV‐induced apoptotic cell death can be lessened in transgenic grouper fish cells.

Renoprotective effects of combination of angiotensin converting enzyme inhibitor with mycophenolate mofetil in diabetic rats - Y. -G. Wu; H. Lin; H Qian; M. Zhao; X. -M. Qi; G. -Z. Wu; S. -T. Lin (Inflammation Research, 2006)

Seismo-Geochemical Variations in SW Taiwan: Multi-Parameter Automatic Gas Monitoring Results - T. F. Yang; C.-C. Fu; V. Walia; C.-H. Chen; L. L. Chyi; T.-K. Liu; S.-R. Song; M. Lee; C.-W. Lin; C.-C. Lin (Pure and Applied Geophysics, 2006)

Protoplast electrofusion between common wheat (Triticum aestivum L.) and Italian ryegrass (Lolium multiflorum Lam.) and regeneration of mature cybrids - T. M. Ge; X. H. Lin; F. L. Qin; S. W. Yu; Y. J. Yu (In Vitro Cellular & Developmental Biology - Plant, 2006)

Nucleotide sequence and mRNA expression analysis of β-actin gene in the orange-spotted grouper Epinephelus coioides - W. M. Zhang; Y. Zhang; L. H. Zhang; S. G. Wang; T. Y. Zhu; D. Lin; G. Z. Ma (Fish Physiology and Biochemistry, 2005)

Characterisation of the welsh onion isolate of Shallot yellow stripe virus from China - J. Chen; C.-B. Wei; H.-Y. Zheng; Y.-H. Shi; M. J. Adams; L. Lin; Q.-Y. Zhang; S.-J. Wang; J.-P. Chen (Archives of Virology, 2005)

Isolation and characterization of actinomycetes antagonistic to pathogenic Vibrio spp. from nearshore marine sediments - J. L. You; L. X. Cao; G. F. Liu; S. N. Zhou; H. M. Tan; Y. C. Lin (World Journal of Microbiology and Biotechnology, 2005)

Phylogenetic analysis of classical swine fever virus in Taiwan - C. H. Pan; M. H. Jong; T. S. Huang; H. F. Liu; S. Y. Lin; S. S. Lai (Archives of Virology, 2005)

Manganese Uptake and Accumulation by Two Populations of Phytolacca acinosa Roxb. (Phytolaccaceae) - S. G. Xue; Y. X. CHEN; A. J. M. Baker; R. D. Reeves; X. H. Xu; Q. Lin (Water, Air, & Soil Pollution, 2005)

Trace Metals in Mosquito Coil Smoke - T.-S. Lin; F.-M. Shen (Bulletin of Environmental Contamination and Toxicology, 2005)

Whole Blood Vanadium in Taiwanese College Students - T.-S. Lin; C.-L. Chang; F.-M. Shen (Bulletin of Environmental Contamination and Toxicology, 2004)

Natural frequency assessment of stability of root keeper magnetic devices - H. -M. Huang; D. -Z. Liu; Y. -Y. Shiau; C. -Y. Yeh; C. -T. Lin; S. -Y. Lee (Medical & Biological Engineering & Computing, 2004)

Mycobacterium Reverse Hybridization Line-Probe Assay Used to Diagnose Disseminated Mycobacterium haemophilum Infection in a Child with Acute Lymphoblastic Leukemia - F. Bosma; J. M. Deckers-Kocken; S. S. N. de Graaf; T. Schlin; W. J. G. Melchers; J. A. Hoogkamp-Korstanje (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Mapping of quantitative trait loci controlling low-temperature germinability in rice (Oryza sativa L.) - K. Fujino; H. Sekiguchi; T. Sato; H. Kiuchi; Y. Nonoue; Y. Takeuchi; T. Ando; S. Y. Lin; M. Yano (Theoretical and Applied Genetics, 2004)

Application of a ?Big-Tree? model to regional climate modeling: a sensitivity study - X.-M. Zeng; M. Zhao; R.-C. Yu; N.-S. Lin; Y.-Q. Zheng; L.-J. Zhang; R.-J. Zhang (Theoretical and Applied Climatology, 2003)

Fine linkage mapping enables dissection of closely linked quantitative trait loci for seed dormancy and heading in rice - Y. Takeuchi; S. Y. Lin; T. Sasaki; M. Yano (Theoretical and Applied Genetics, 2003)

Surfactant proteinA and B genetic variants predispose to idiopathic pulmonary fibrosis - Moises Selman; Hung-Mo Lin; Martha Montao; Audrey L. Jenkins; Andrea Estrada; Zhenwu Lin; Guirong Wang; Susan L. DiAngelo; Xiaoxuan Guo; Todd M. Umstead; C. Max Lang; Annie Pardo; et al. (Human Genetics, 2003)

Cariporide enhances lactate clearance upon reperfusion but does not alter lactate accumulation during global ischaemia - H. Lin; M.-S. Suleiman (Pflügers Archiv - European Journal of Physiology, 2003)

Prospective study of serum retinol, β-carotene, β-cryptoxanthin, and lutein/zeaxanthin and esophageal and gastric cancers in China - Christian C. Abnet; You-Lin Qiao; Sanford M. Dawsey; Dennis W. Buckman; Chung S. Yang; William J. Blot; Zhi-Wei Dong; Philip R. Taylor; Steven D. Mark (Cancer Causes & Control, 2003)

Gene content and organization of an 85-kb DNA segment from the genome of the phytopathogenic mollicute Spiroplasma kunkelii - Y. Zhao; R. W. Hammond; R. Jomantiene; E. L. Dally; I.-M. Lee; H. Jia; H. Wu; S. Lin; P. Zhang; S. Kenton; F. Z. Najar; A. Hua; et al. (Molecular Genetics and Genomics, 2003)

Detection ofBurkholderia pseudomallei in rice fields with PCR-based technique - C. M. Kao; S. C. Chen; Y. S. Chen; H. M. Lin; Y. L. Chen (Folia Microbiologica, 2003)

Trace Metals in Chinese Joss Stick Smoke - T.-S. Lin; F.-M. Shen (Bulletin of Environmental Contamination and Toxicology, 2003)

Dissecting the pet18mutation in Saccharomyces cervisiae: HTL1encodes a 7-kDa polypeptide that interacts with components of the RSC complex - Y.-M. Lu; Y.-R. Lin; A. Tsai; Y.-S. Hsao; C.-c. Li; M. Y. Cheng (Molecular Genetics and Genomics, 2003)

Trace Metals in Candle Smoke - T.-S. Lin; F.-M. Shen; J.-L. Chen; M.-H. Yang (Bulletin of Environmental Contamination and Toxicology, 2003)

Involvement of the terminus of grouper betanodavirus capsid protein in virus-like particle assembly - M. W. Lu; C. S. Lin (Archives of Virology, 2003)

A framework for integrating the songbird brain - Jarvis E.; Smith V.; Wada K.; Rivas M.; McElroy M.; Smulders T.; Carninci P.; Hayashizaki Y.; Dietrich F.; Wu X.; McConnell P.; Yu J.; et al. (Journal of Comparative Physiology A, 2002)

Specific detection ofPythium aphanidermatum from hydroponic nutrient solution by booster PCR with DNA primers developed from mitochondrial DNA - P. H. Wang; L. M. Boo; Y. S. Lin; Y. Yeh (Phytoparasitica, 2002)

Residential Water Supply as a Likely Cause of Community-Acquired Legionnaires' Disease in an Immunocompromised Host - Chen Y-S.; Lin W-R.; Liu Y-C.; Chang C-L.; Gan V-L.; Huang W-K.; Huang T-S.; Wann S-R.; Lin H-H.; Lee S.; Huang C-K.; Chin C.; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Stratification and seasonal stability of diverse bacterial communities in a Pinus merkusii (pine) forest soil in central Java, Indonesia - Agna S. Krave; Bin Lin; Martin Braster; Anniet M. Laverman; Nico M. van Straalen; Wilfred F. M. Röling; Henk W. van Verseveld (Environmental Microbiology, 2002)
Summary In Java, Indonesia, many nutrient‐poor soils are intensively reforested with Pinus merkusii (pine). Information on nutrient cycles and microorganisms involved in these cycles will benefit the management of these important forests. Here, seasonal effects on the stratification of bacterial community structure in the soil profile of a tropical pine forest are described, and differences in bacterial communities are related to chemical and physical soil parameters. Culture‐independent community profiles of litter, fragmented litter and mineral soil layers were made by denaturing gradient gel electrophoresis (DGGE) of 16S rDNA‐specific polymerase chain reaction (PCR) fragments. The community profiles of the different soil layers clustered separately, correlating with significant differences in organic matter content between the three layers. The bacterial communities appeared to be stable during the wet season of 1998. The drought in 1997, caused by the El Niño climatic effect, did not influence the bacterial communities in fragmentation and mineral soil, although moisture content and other soil parameters were markedly lower than in the wet season. However, communities in litter were influenced by drought. In the litter layer, the moisture content was significantly lower than in the fragmentation and mineral layers during the dry season. A clone library was made from a litter sample taken during the wet season. Partial sequencing of 74 clones and linking the DGGE banding positions of these clones to bands in the DGGE profile of the sample from which the clone library was derived showed considerable bacterial diversity. Alpha‐proteobacteria (40.5% of the clones, of which 57% belonged to the Rhizobium–Agrobacterium group) and high‐G+C content, Gram‐positive bacteria (36.5%) dominated the clone library.

Mapping quantitative trait loci controlling seed longevity in rice (Oryza sativa L.) - K. Miura; S. Lin; M. Yano; T. Nagamine (Theoretical and Applied Genetics, 2002)

Genetic dissection of a genomic region for a quantitative trait locus, Hd3, into two loci, Hd3a and Hd3b, controlling heading date in rice - L. Monna; H. Lin; S. Kojima; T. Sasaki; M. Yano (Theoretical and Applied Genetics, 2002)

A genetic linkage map of Nicotiana plumbaginifolia/ Nicotiana longiflora based on RFLP and RAPD markers - T. Y. Lin; Y. Y. Kao; S. Lin; R. F. Lin; C. M. Chen; C. H. Huang; C. K. Wang; Y. Z. Lin; C. C. Chen (Theoretical and Applied Genetics, 2001)

Sphingolipids as biomarkers of fumonisin exposure and risk of esophageal squamous cell carcinoma in China - Christian C. Abnet; Craig B. Borkowf; You-Lin Qiao; Paul S. Albert; Elaine Wang; Alfred H. Merrill; Steven D. Mark; Zhi-Wei Dong; Philip R. Taylor; Sanford M. Dawsey (Cancer Causes & Control, 2001)

Rapid molecular analysis of the haemagglutinin gene of human influenza A H3N2 viruses isolated in Spain from 1996 to 2000 - M. T. Coiras; J. C. Aguilar; M. Galiano; S. Carlos; V. Gregory; Y. P. Lin; A. Hay; P. Pérez-Breña (Archives of Virology, 2001)

Bioaccumulation of Arsenic in Aquacultural Large-Scale Mullet Liza macrolepis from Blackfoot Disease Area in Taiwan - M.-C. Lin; C.-M. Liao; C.-W. Liu; S. Singh (Bulletin of Environmental Contamination and Toxicology, 2001)

Distribution of glucose-6-phosphate dehydrogenase mutations in Southeast Asia - Kuni Iwai; Akira Hirono; Hiroyuki Matsuoka; Fumihiko Kawamoto; Toru Horie; Khin Lin; Indah S. Tantular; Yoes P. Dachlan; Harsono Notopuro; Noor I. Hidayah; Abdul M. Salim; Hisaichi Fujii; et al. (Human Genetics, 2001)

Toward the mapping of physiological and agronomic characters on a rice function map: QTL analysis and comparison between QTLs and expressed sequence tags - K. Ishimaru; M. Yano; N. Aoki; K. Ono; T. Hirose; S. Y. Lin; L. Monna; T. Sasaki; R. Ohsugi (Theoretical and Applied Genetics, 2001)

Blood and Urine Cadmium Levels in Relation to Demographic and Life Style in Middle Aged and Elderly Men - Y. C. Chen; Y. S. Pu; R. S. Lin; C. Y. Yang; M. K. Lai; S. H. Liu; F.-C. Sung (Bulletin of Environmental Contamination and Toxicology, 2001)

Aliphatic Aldehydes Produced by Heating Chinese Cooking Oils - J.-M. Lin; S.-J. Liou (Bulletin of Environmental Contamination and Toxicology, 2000)

Differential expression of dystrophin, utrophin, and dystrophin-associated proteins in human muscle culture - V. Radojevic; S. Lin; J.-M. Burgunder (Cell and Tissue Research, 2000)

Aliphatic Aldehydes Produced by Heating Chinese Cooking Oils - J.-M. Lin; S.-J. Liou (Bulletin of Environmental Contamination and Toxicology, 2000)

Development of a plant regeneration system based on friable embryogenic callus in the ornamental Alstroemeria - H. -S. Lin; C. van der Toorn; K. J. J. M. Raemakers; R. G. F. Visser; M.J. De Jeu; E. Jacobsen (Plant Cell Reports, 2000)

Rapid early onset lymphocyte cell death in mice resistant, but not susceptible to Leishmania major infection - Julie Desbarats; Jeffrey E. Stone; Lin Lin; Zahra F. Zakeri; Gerald S. Davis; Linda M. Pfeiffer; Richard G. Titus; M. Karen Newell (Apoptosis, 2000)

Cadmium-Inducible Metallothionein in Tilapia ( Oreochromis mossambicus ) - S. M. Wu *, , C. F. Weng; M. J. Yu; C. C. Lin; S. T. Chen; J. C. Hwang; P. P. Hwang (Bulletin of Environmental Contamination and Toxicology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Familial clustering of rheumatoid arthritis with other autoimmune diseases - Jing-Ping Lin; Joseph M. Cash; Sharon Z. Doyle; Sandra Peden; Keith Kanik; Chris I. Amos; S. J. Bale; Ronald L. Wilder (Human Genetics, 1998)

Fine mapping of quantitative trait loci Hd-1, Hd-2 and Hd-3, controlling heading date of rice, as single Mendelian factors - T. Yamamoto; Y. Kuboki; S. Y. Lin; T. Sasaki; M. Yano (Theoretical and Applied Genetics, 1998)

Mapping quantitative trait loci controlling seed dormancy and heading date in rice, Oryza sativa L., using backcross inbred lines - S. Y. Lin; T. Sasaki; M. Yano (Theoretical and Applied Genetics, 1998)

Maturation-dependent gene expression in a conditionally transformed liver progenitor cell line - A. S. Fiorino; A. M. Diehl; H. Z. Lin; I. R. Lemischka; L. M. Reid (In Vitro Cellular & Developmental Biology - Animal, 1998)

Transgenic peppermint ( Mentha × piperita L.) plants obtained by cocultivation with Agrobacterium tumefaciens - X. Niu; K. Lin; P. M. Hasegawa; R. A. Bressan; S. C. Weller (Plant Cell Reports, 1998)

Mapping quantitative trait loci associated with regeneration ability of seed callus in rice, Oryza sativa L. - F. Taguchi-Shiobara; S. Y. Lin; K. Tanno; T. Komatsuda; M. Yano; T. Sasaki; S. Oka (Theoretical and Applied Genetics, 1997)

Direct shoot regeneration from excised leaf explants of in vitro grown seedlings of Alstroemeria L. - H. S. Lin; M. J. De Jeu; E. Jacobsen (Plant Cell Reports, 1997)

CaEGTA uncompetitively inhibits calcium activation of whorl morphogenesis inAcetabularia - Lionel G. Harrison; G. Donaldson; W. Lau; M. Lee; B. P. Lin; S. Lohachitranont; I. Setyawati; J. Yue (Protoplasma, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Sweet potato (Ipomoea batatas) trypsin inhibitors expressed in transgenic tobacco plants confer resistance against Spodoptera litura - K.-W. Yeh; M.-I. Lin; S.-J. Tuan; Y.-M. Chen; C.-J. Lin; S.-S. Kao (Plant Cell Reports, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Envelope gene sequences of human T-lymphotropic virus type I in Taiwan - M. T. Lin; Y. C. Chen; P. J. Chen; Y. C. Yang; J. L. Tang; J. M. Wu; S. E. Chuang; C. S. Yang (Archives of Virology, 1996)

Evolutionary study on the coxsackievirus A 24 variant causing acute hemorrhagic conjunctivitis by oligonucleotide mapping analysis of RNA genome - K. Miyamura; N. Takeda; M. Tanimura; T. Ogino; S. Yamazaki; C. -W. Chen; K. -H. Lin; S. Y. Lin; A. Ghafoor; M. Yin-Murphy (Archives of Virology, 1990)

Acute hepatotoxicity of a tetrachlorobiphenyl?Changes in the hepatocyte ultrastructure and plasma membrane-bound enzymes - F. S. Lin; M. T. Hsia; J. R. Allen (Archives of Environmental Contamination and Toxicology, 1979)